Hyperspectral multi-indicator ripeness perception model for mechanized harvesting of “Yulu Xiang” pears - Na Ma; Jinyan Sun; Yingjun Li; Shijun Sun; Chenfei Li; Yile Sun; Zonglin Liu; Wendong Niu; Xiaoqin Xue; Haiyan Song (Computers and Electronics in Agriculture, 2026)

Unraveling the mechanism of gluten protein restructuring in modulating the cracking behavior of dumpling wrappers during freeze-thaw cycles - Li-Qin Tang; Xiaohong Sun; Xiao-Na Guo; Ke-Xue Zhu (Food Hydrocolloids, 2026)

Icaritin improves pregnancy outcomes in endometriosis by inhibiting ovarian granulosa cell senescence - Yalun He; Jie Ding; Yangshuo Li; Ji Sun; Cuiping Wei; Na Sun; Runnan Jiang; Ziming Zhao; Xiaolan Liang; Yiming Chen; Wen Cheng; Litai Zhang; et al. (Molecular Biology Reports, 2026)

First record of Brachyphyllum (Cheirolepidiaceae) from the Lower Jurassic of the Ordos Basin, China: Paleogeographic and paleoclimatic implications linked to T-OAE - Chao-Hui Wei; Yun-Feng Li; Chang-Lu Zhang; Xiao Tan; Fei Liang; Chun-Lin Sun; Tao Li; Yu-Ling Na (Review of Palaeobotany and Palynology, 2026)

Experimental investigation on adiabatic two-phase frictional pressure drop of R32, R1234ze(E), and their mixtures in a horizontal minichannel - Na Liu; Yeyi Liu; Hao Ji; Dezheng Sun; Run Li; Chuandian Dong; Huan Lin (International Journal of Refrigeration, 2026)

Temporal variation in secondary metabolites and antioxidant activity during the biotransformation of American ginseng by Monascus purpureus MN 001: Molecular docking analysis of β-glucosidase-mediated ginsenoside hydrolysis - Li Zhang; Zirui Liu; Boyuan Zhang; Miaomiao Yang; Xueling Zhao; Siliang Lyu; Jiahao Bai; Siyuan Bai; Na Liu; Zhongke Sun; Peng Li; Chengwei Li; et al. (Food Bioscience, 2026)

Optimized decarbonization pathway coupled with carbon trading mechanism for China's steel industry towards carbon neutrality - Jingchao Sun; Hongming Na; Honggang Pan; Tao Du; Yuxing Yuan; Ziyang Qiu; Lei Zhang; Yingnan Li; Jie Cui; Yong Sun (Energy Policy, 2026)

A triboelectric sensor array based on facial muscle-action unit-emotion mapping toward astronaut psychological monitoring in long-term missions - Xuyan Hou; Huiyuan Jing; Meiyang Zhang; Fengyan Liu; Ruiwen Zhao; Zhonglai Na; Pingting Zhao; Yuhui Liu; Ximing Zhao; Linbo Xin; Jian Zhou; Xi Chen; et al. (Chemical Engineering Journal, 2026)

Enhancing bread storage stability with chitosan oligosaccharides of different molecular weights: inhibiting spoilage microorganisms and retarding starch retrogradation - Li-Hong Du; Xiao-Na Guo; Xiao-Hong Sun; Ke-Xue Zhu (Carbohydrate Polymers, 2026)

A heparan-like glycosaminoglycan from the white jade snail: Precise structural elucidation, alkaline-induced artificial changes, and non-anticoagulant heparanase inhibition - Pin Wang; Na Gao; Qijiang Mao; Lutan Zhou; Yu Wang; Ying Pan; Fengyun Wu; Penghao Kang; Zanyang Min; Yujun Ma; Huifang Sun; Xiang Shi; et al. (Carbohydrate Polymers, 2026)

Corrigendum to “Fermented Chinese herbal medicines combined with probiotics promote growth of fattening lambs under heat stress by modulating rumen mucosal barrier functions” [Anim. Feed Sci. Technol. 326 (2025) 116384] - Shoupei Zhao; Xinsheng Sun; Na Zhao; Hongwei Zhang; Gaofu Wang; Lu Zhang; Yuqing Liu; Haitong Yang; Jianjie Li; Jia Zhou; Yuhong Gao (Animal Feed Science and Technology, 2026)

Biochar enhances soil carbon in iron-rich red soil but fails in calcareous fluvo-aquic soil: Mineral protection outweighs microbial turnover - Wanyi Fang; Peipei Li; Ge Song; Na Deng; Siyi Liu; Tianran Sun; Limei Zhang (Agriculture, Ecosystems & Environment, 2026)

Environment and human-health related rodent acute oral toxicity assessment of aniline compounds and their derivatives using QSTR and q-RASTR-based new approach methodologies - Jinxu Li; Shuo Chen; Tengjiao Fan; Ting Ren; Na Zhang; Lijiao Zhao; Rugang Zhong; Zhirong Sun; Guohui Sun (Journal of Hazardous Materials, 2026)

Annual energy use and economic performance of rice-based cropping systems: A three-year field study in Southwest China - Chuanhai Shu; Qingyue Cheng; Binbin Liu; Hongkun Xie; Yuanqing Shi; Mingming Hu; Hao Fu; Peng Ma; Na Li; Zhonglin Wang; Zongkui Chen; Yongjian Sun; et al. (Journal of Cleaner Production, 2026)

Controlling the properties of 3D-printed sodium caseinate emulsion gels by tuning starch-induced network architecture - Kangning Zhang; Fangyuan Tian; Xiaojing Li; Shengju Ge; Yanping Wang; Yang Qin; Man Li; Rongbo Fan; Qingjie Sun; Na Ji (Food Research International, 2026)

Inhibition of digestive enzymes with EGCG-loaded inverse alginate beads: a strategy for modulating starch digestion - Xiya Zhang; Jinling Zou; Shengju Ge; Xiaojing Li; Meng Li; Yang Qin; Man Li; Qingjie Sun; Jian He; Na Ji (Food Chemistry, 2026)

Zein-calcium alginate dual-shell liquid-core beads for tailored starch digestibility: Structural design, functional performance, and mechanistic analysis - Yang Qin; Xiya Zhang; Jinling Zou; Shengju Ge; Xiaojing Li; Man Li; Qingjie Sun; Qingze Han; Huanying Qin; Jian He; Na Ji (Food Chemistry, 2026)

Polystyrene microplastic exposure induces hepatic damage via immune-modulated autophagy and ferroptosis in Nile tilapia (Oreochromis niloticus) - Feilong Wang; Xiaolong Fan; Xiaomeng Guo; Na Guo; Tian Gao; Changle Zhao; Yuanyuan Li; Haiyan Xu; Fan Bai; Yixin Chen; Deshou Wang; Lina Sun; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Spatiotemporal immune responses and targeted therapeutic strategies in the immune microenvironment of ischemic stroke - Na Yin; Yuqi Sun; Shuxuan Li; Huiyang Ji; Xinru Zhang; Shaohui Liu; Wang Wang; Jinjin Shi; Pengju Wang (Chemical Engineering Journal, 2026)

Multi-omics integrated analysis reveals the key metabolic regulation mechanisms of petal color in Phalaenopsis aphrodite Rchb.f - Yuqing Sun; Na Meng; Ping Li; Tingting Ren; Chunyan Dong; Chunling Wang; Siqi Ma; Yiqiang Li (Plant Cell Reports, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Effective removal of PFAS by a novel multifunctional microbubble-mediated cathodic adsorption process - Yang Li; Yixin Zhang; Chaoyong Sun; Yuxiao Zhang; Na Zhang; Yujue Wang (Water Research, 2026)

Freeze-thaw perturbation decreases priming of soil organic carbon mineralization induced by straw return in croplands - Meng Na; Mengqin Xiang; Yifan Wang; Haifeng Lu; Jihai Zhou; Chunjie Tian; Lu-Jun Li; Yuqing Miao; Hailong Sun; Shangqi Xu; Johannes Rousk (Soil Biology and Biochemistry, 2026)

High abundance of small-sized microplastics in transport ship domestic sewage: Characteristics and potential ecological risks - Qing Su; Yuxia Li; Lingna Kong; Na Lu; Ling Qu; Yuyang Sun; Xiaodan Zhang; Xiaomeng Wang (Regional Studies in Marine Science, 2026)

Co-fermentation of Ampelopsis grossedentata with Camellia sinensis reduces bitterness, enhances sweet aroma, and generates novel bioactive theaflavin analogues - Si-Rui Li; Zi Yang; Na Song; Jia-Yi Li; Yu-Xing Zhang; Hao Li; Peng Zhang; Yu-Lan Song; Yu Sun; Kun Qian; Da-Wei Zhang; Guan-Hu Bao (Food Chemistry, 2026)

Detection and Defense Against False Data Injection Attacks for Secure Energy Management in Hybrid Electric Ships - Hao Sun; Na Li; Mo Guo; Jingwei Wei; Tianqing Yuan (Journal of Marine Science and Engineering, 2026)
Reliable battery state awareness is essential for energy management and power allocation in hybrid electric ships. However, battery management systems are increasingly exposed to False Data Injection Attacks (FDIAs) in intelligent connected environments, which can distort State of Charge (SOC) estimation and compromise the operational reliability of shipboard power systems. To address this challenge, this paper proposes a closed-loop “Modeling-Detection-Defense” framework for secure SOC estimation in marine cyber-physical energy systems. First, a stealthy FDIA model is developed based on battery dynamics and physical consistency constraints. Second, a hybrid detection method combining unsupervised and supervised learning is proposed to identify attacks. Finally, a long short-term memory network is employed to reconstruct compromised measurements and provide reliable SOC information for continuous energy management. Experimental results demonstrate that the proposed framework mitigates SOC estimation deviations caused by FDIAs. In addition, it effectively reduces power allocation errors and energy losses, thereby improving the cyber-resilience, operational reliability, and energy efficiency of hybrid ship power systems.

Chronic intermittent hypoxia sustains the low-grade inflammatory memory of monocytes via activation of myelopoiesis - Shi Qi Li; Yi Wang; Meng Yao Li; Liu Zhang; Xi Xi Chen; Ying Ni Lin; Li Na Zhou; Xian Wen Sun; Yong Jie Ding; Qing Yun Li (Inflammation Research, 2026)

Establishment and identification of an embryonic cell line of Chinese sturgeon (Acipenser sinensis) and its application in germplasm conservation and disease resistance - Qi Zhang; Juanjuan Liu; Zhihong Gong; Wenjie Li; Chenfei Guo; Jiaqi Mai; Yuqi Sun; Songlin Chen; Na Wang (Aquaculture, 2026)

The molecular sieve to component flow transition in oil expulsion from shales: insights from semi-confined pyrolysis of saline lacustrine shale - Zhushi Ge; Xiaoping Liu; Chang Chen; Xiaoguang Li; Yongcheng Chen; Xingzhou Liu; Zilong Zhang; Biao Sun; Yi Zhong; Na Gao; Wenhui Xie (Organic Geochemistry, 2026)

Preparation of negative carbon cement soil by corn straw biochar collaborative carbonization technology: Mechanical properties, carbon sequestration evaluation, microscopic mechanism - Pengfei Wei; Wei Wang; Xukun Ma; Na Li; Chenjun Wang; Yong Liu; Ping Jiang; Miaomiao Sun (Journal of Environmental Management, 2026)

Co-precipitated protein prepared by soybean protein and phycocyanin: Focus on protein structure and nutritional characteristics - Na Sun; Zhe Wang; Jianan Li; Lanxin Li; Shi Liu; Jianling Feng; Ruihan Su; Xiaohong Tong; Huan Wang; Lianzhou Jiang (Food Chemistry, 2026)

A diatom-inspired tissue adhesive for wound sealing and hemostasis under extreme physiological conditions - Furui Qu; Xiaojie Sun; Mingxia Feng; Xiaoye Wang; Yan Zhang; Zicheng Xia; Yang Yang; Xiguang Chen; Na Li; Chao Feng (Chemical Engineering Journal, 2026)

Detachable TMSD-CRISPR for programmable and highly specific discrimination of DNA/RNA mutations - Yiqi Zhang; Wang Luo; Yaoyi Zhang; Yu He; Li Zhang; You Wu; Kejia Wu; Hongyan Yu; Xiaole Han; Na Yin; Jiu Pu; Dan Bai; et al. (Chemical Engineering Journal, 2026)

Correction to: Cardioprotective effects of notoginsenoside R1 on myocardial remodeling and cardiac function in restraint stress‑induced MI in rats - Peng Sun; Cuiyu Han; Qian Sun; Tingting Li; Lan Li; Mingxing Shi; Pei Zhao; Lu Chen; Na Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Intestinal transcriptomic responses to chronic carbonate alkalinity stress in grass carp (Ctenopharyngodon idella) - Feng Li; Tianqi Liu; Kexin Zhang; Zhipeng Sun; Rongbin Na; Yumei Chang; Cuiyun Lu; Xianhu Zheng (Aquaculture International, 2026)

Real-Time Monitoring of Anaesthetic-Induced Change of Consciousness States Associated with Brain Biophoton Information Integration - Na Liu; Qiao Wei; Chengming Xia; Jinzhong Li; Chunli Qin; Yan Sun; Zhuo Wang; Hao Lei; Jiapei Dai (Neuroscience Bulletin, 2026)

PPAOT predictor: ARKA-RASTR strategy-driven rodent acute oral toxicity prediction for pyrazole and pyrrolidine scaffolds-based chemicals with intelligent mechanistic interpretation - Jianing Xu; Shuo Chen; Ting Ren; Feifan Li; Na Zhang; Lijiao Zhao; Rugang Zhong; Guohui Sun (Archives of Toxicology, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Continuous plastic film mulching reduces global warming potential (GWP) in greenhouse soil biosolarization by regulating microbial carbon and nitrogen metabolism - Qianru Liu; Qiang Zuo; Yuteng Qi; Yufan Yang; Guochun Ding; Mao Li; Guicheng Han; Yinzhi Chu; Bingxue Wang; Yuhao Sun; Xiao Zhao; Lianfeng Du; et al. (Journal of Cleaner Production, 2026)

Straw mulching combined with alternate wetting and drying reduces methane emissions in paddy fields: associations with carbon availability and methanogenic archaeal community shifts - Chuanhai Shu; Zhonglin Wang; Binbin Liu; Yue Huang; Yuanqing Shi; Hongkun Xie; Mingming Hu; Qingyue Cheng; Qin Liao; Na Li; Zongkui Chen; Yongjian Sun; et al. (Journal of Environmental Management, 2026)

Synergistic effects of starch blending and retrogradation control on the quality improvement of instant fresh rice noodles - Hao Li; Minghang Guan; Zihui Xu; Chi Zhang; Liu Xiong; Na Ji; Qingjie Sun (Food Chemistry, 2026)

Physicochemical characteristics changes in post-ripening of wheat flour mill streams: Effects on dough properties and steamed bread quality - Meng-Li Zhang; Xiao-Na Guo; Xiao-Hong Sun; Ke-Xue Zhu (Food Hydrocolloids, 2026)

Time and pH regulation of the morphology and structure evolution of soybean protein fibrils: Focusing on foaming mechanism and application - Jianan Li; Zhe Wang; Bowen Yang; Xinhui Peng; Shi Liu; Na Sun; Ruihan Su; Xiaohong Tong; Huan Wang; Lianzhou Jiang (Food Hydrocolloids, 2026)

Protective effects of melatonin on mouse ovarian tissue against oxidative stress and ferroptosis may involve the MT1 receptor - Sheng Nan Jiang; Xin Zhang; Li Na Si; Meng Wei; Xin Hui Wei; Yong Wei Wang; Tie Cheng Sun; Song He Yang; Zhi Hong Chen; Lu Yang Cheng (Cryobiology, 2026)

Time-dependent biphasic dysregulation of autophagy and innate immunity underlies polystyrene microplastics-induced hepatotoxicity in Nile tilapia - Feilong Wang; Xiaomeng Guo; Na Guo; Xiaolong Fan; Haiyan Xu; Yuanyuan Li; Tian Gao; Yixin Chen; Changle Zhao; Lina Sun; Deshou Wang; Xin Xie; et al. (Aquatic Toxicology, 2026)

Synergistic effects of iron tailings and maize straw on soil compression: roles of sand content and organic carbon - Aobo Sun; Changdong Han; Yanyu Han; Jiaqi Li; Jing An; Guangyan Liu; Na Yu; Hongtao Zou; Hongdou Liu (Journal of Soils and Sediments, 2026)

FTO-Mediated m6A Demethylation of MZF1 Regulates DECR1 to Promote Fatty Acid Oxidation and Exacerbate Myocardial Ischemia/Reperfusion Injury - Jin Tian; Qian He; Na Li; Yuehui Sun; Anxin Zhang; Haixiong Wang (Biochemical Genetics, 2026)

Regulated cell death: a multidimensional regulatory network in the pathogenesis of renal fibrosis - Wen Li; Liang Zhou; Jinji Zhang; Jingying Sun; Qing Feng; Kunyi Wu; Na Zhu (Apoptosis, 2026)

Runoff evolution and attribution analysis over the past 40 years in Xiangjiang River Basin, China - Jin Xiang; Liu Yang; Chang Feng; Ruisi Sun; Chang Liu; Na Li (Environment, Development and Sustainability, 2026)

PFOS promotes Alzheimer’s disease through aggravating the cell apoptosis and AKT/GSK3β/NF-κB/NLRP3 pathway mediated inflammation - Ming Li; Xianhao Ping; Huixin Song; Jin Sun; Qian Yang; Li-Na Gao (Toxicology, 2026)

Evidence for Early Middle Jurassic wildfires: New macro-charcoal records from the Xishanyao Formation, Junggar Basin, Northern Xinjiang, China - Bing Yang; Yuling Na; Xiao Shi; Yi Wei; Xinzhi Zhang; Bing Wang; Siyuan Sun; Weitong Li (Review of Palaeobotany and Palynology, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Exploration of chicken lung antioxidant peptides modified by plastein reaction: Purification, identification and molecular docking - Jingwen Jia; Siyu Cheng; Lisheng Li; Tian Chen; Na Xu; Xiaomei Sun; Yun Bai; Xinglian Xu; Minyi Han (Food Bioscience, 2026)

Atrazine increases hepatic inflammation and injury via endoplasmic reticulum (ER) stress mediated excessive formation of mitochondria-associated membranes (MAMs) and activation of the cGAS-STING pathway - Zi-Jun Sun; Guan-Yue Shan; Hui Wan; Yu-Xin Zhang; Zhi-Cheng Gao; Wen-Na Shi; Lei Lv; Wei-Qun Yan; Hai-Jun Li (Environmental Pollution, 2026)

Crystal phase-dependent ZrO2 for fluoride adsorption in hydrochloric acid - Qian Wu; Xin Huang; Shiyu Sun; Yan Li; Fengzhen Liu; Xin Chen; Na Wang; Ting Wang; Zijian Zhou; Bin Lu; Hongxun Hao (Journal of Environmental Chemical Engineering, 2026)

Asynchronous abrupt changes of lake ecosystems in the Anthropocene - Dinggui Wu; Tian Xia; Qingfeng Zhao; Yibin Sun; Na Song; Man Li; Tianchen He (Global and Planetary Change, 2026)

Effects of Pediococcus pentosaceus and tea polyphenols on biogenic amines, volatile compounds, and microbial Community in Fermented Sausage - Erke Sun; Xueying Sun; Weiqi Qin; Shiqi Hao; Yanrong Chen; Lina Sun; Ye Jin; Na Wang; Rugang Tian; Hui Li; Jie Kang; Xun Xiao; et al. (Food Chemistry, 2026)

Improvement of the quality of whole grain highland barley slurry through thermal pre-treatment under turbulent conditions: Lubrication, microstructure, and rheological - Bo-Hui Li; Yi-Peng Bai; Xiao-Na Guo; Xiao-Hong Sun; Ke-Xue Zhu (Food Chemistry, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Mechanistic insights into efficient H2O2 production by a carbon nitride homojunction under different conditions - Guangyuan Li; Binrong Li; Na Li; Wei Gao; Yongqi Shao; Xin Li; Wenli Li; Wei Nie; Feiteng Sun; Jingyuan Huang; Qi Gong; Xuedong Wang (Chemical Engineering Journal, 2026)

Erzhi pills: a potential aging-modulating agent targeting immunosenescence in mice - Zhirui Fang; Wei Sun; Na Li; Tingting Shi; Xiuyun Ren; Rui Zhang; Yujing Zhang; Jing Chen; Qi Liu; Meng Wang; Lu Chen; Hong Wang (Biogerontology, 2026)

Methanobrevibacter smithii induces postnatal growth retardation through blunting hepatic ketone body metabolism - Ming Qi; Tongxing Song; Yuankun Deng; Na Li; Nan Wang; Andong Zha; Qing Ye; Chengming Wang; Yirui Shao; Yucheng Zhu; Ming Sun; Jens Walter; et al. (Science Bulletin, 2026)

Longitudinal profiling of toxigenic fungi and mycotoxin risks in Coix lacryma-jobi L. - Anqi Xu; Yan Xu; Yuhui Yang; Fan Sun; Hua Cai; Yin Zhu; Xiaohui Xu; Xiushi Li; Aibo Wu; Na Liu (Journal of Hazardous Materials, 2026)

Experimental investigation on adiabatic two-phase frictional pressure drop of R290, R600a, and their mixtures in a horizontal minichannel - Na Liu; Hao Ji; Yeyi Liu; Run Li; Dezheng Sun; Qian Zhao; Jianxiang Guo (International Journal of Refrigeration, 2026)

Stability, digestive, and absorptive properties of astaxanthin ester-loaded Pickering emulsions evaluated using in vitro and in vivo models - Lu Yang; Xiaohui Liu; Hongwei Zheng; Na Ji; Hongyan Li; Jie Xu; Qingjie Sun; Changhu Xue (Food Research International, 2026)

Impacts of gluten aggregation behavior on the gassing properties of steamed bread during the wheat flour post-ripening - Meng-Li Zhang; Xiao-Na Guo; Xiao-Hong Sun; Ke-Xue Zhu (Food Hydrocolloids, 2026)

Pollen exposure and risk of childhood allergic diseases in a semi-arid Region: Effects of pollen types and seasons - Kunqi Liu; Ziming Li; Huimin Liu; Feng Ma; Na Gao; Tianfeng Deng; Shaobo Zhang; Zhaobin Sun (Environmental Research, 2026)

3D hybrid chiral metamaterial with diverse lateral deformation behaviors: Theoretical, experimental, and numerical study - Yu Zhang; Weizhu Yang; Peijie Sun; Junming Huang; Na Yang; Lei Li (Engineering Structures, 2026)

Cardioprotective effects of notoginsenoside R1 on myocardial remodeling and cardiac function in restraint stress-induced MI in rats - Peng Sun; Cuiyu Han; Qian Sun; Tingting Li; Lan Li; Mingxing Shi; Pei Zhao; Lu Chen; Na Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Effects of two-stage illumination strategy on the growth and nutrient composition of Chlorella sp. - Zhujun Qiu; Yuande Zhang; Yuqing Wang; Wenyu Zhao; Chonghui Fan; Yao Zhang; Ziyi Sun; Na Li; Qian Zhang (Algal Research, 2026)

Pathogenicity of Porcine reproductive and respiratory syndrome virus in the reproductive system of female piglets: Pathological damage to the uterine horns and developmental arrest - Yi-Xin Yan; Ying Guan; Lei Zhao; Han-Yu Li; Tong Xu; Li-Na Shao; Si-Yuan Lai; Yi Qing; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; et al. (Veterinary Microbiology, 2026)

Alkalized lychee-shell TiO2/WO3-5 heterojunctions with oxygen vacancies for enhanced CO2 photoreduction to methanol - Nan Xiang; Huajun Sun; Guifeng Tang; Na Zhang; Chuanhui Gao; Yuetao Liu; Chuanxing Wang; Junwei Ding; Li Ding (Journal of Environmental Chemical Engineering, 2026)

Geochemical signatures, hydrocarbon generation kinetics, and oil-source correlation of the Es4 member source rocks in the Liaohe Western depression: implications for tight oil exploration in continental rift basins - Zhushi Ge; Xiaoping Liu; Xiaoguang Li; Yongcheng Chen; Chang Chen; Zilong Zhang; Biao Sun; Yi Zhong; Xueyou Tan; Gaohang Jia; Yu Xia; Zuowei Li; et al. (Fuel, 2026)

Global disparities and climatic-economic drivers of micro/nanoplastic accumulation in animals and humans - Na Xiao; Fei Wang; Shuai Ma; Manman Cao; Junhong Li; Ruiyi Xie; Ke Sun (Environmental Pollution, 2026)

Synergistic engineering of a whole-cell catalyst immobilized on bimetallic CaZn-MOF for efficient PET Depolymerization - Yun-kang Chang; Xiao-huan Liu; Nan-Li; Jun-li Jin; Hai-tong Sun; Shuo Li; Fei-fei Zhang; Yu-xuan Song; Xin-hong Yu; Qi-zhi Cao; Fei Liu; Na Xu; et al. (Chemical Engineering Journal, 2026)

A DAMP- and antigen-capturing nanosponge designed as personalized cancer vaccine - Ting Meng; Weikai Sun; Chuanning Wang; Han Yang; Yafei Qi; Daqian Sun; Bingrun Song; Bingzhao Li; Aixin Song; Na Sun; Zhiliang Gao; Dexin Yu (Chemical Engineering Journal, 2026)

Unveiling the genetic architecture of stripe rust resistance in wheat: a region-specific GWAS in Xinjiang, China - Feifei Zhang; Rong Wang; Wenjuan Jiao; Wanlong He; Yuzhe Zhang; Na Sun; Bin Bai; Kemei Li; Yukun Cheng; Hongwei Geng (Theoretical and Applied Genetics, 2026)

Estuarine plumes: Modulators of dissolved organic matter molecular signatures and biogeochemical fate in coastal ecosystems - Guodong Sun; Na Wang; Wenbo Wang; Yihui Guo; Juan Xu; Zijia Zeng; Penghui Du; Penghui Li; Chen He; Quan Shi; Dongxiao Wang; Wei Xie (Marine Pollution Bulletin, 2026)

Analyzing the nitrogen transformation mechanisms in anaerobic digestion of sewage sludge enhanced by thermal hydrolysis pretreatment - Ruiyi Xie; Dan Xu; Shuai Ma; Manman Cao; Junhong Li; Na Xiao; Ke Sun; Ruiping Liu; Fei Wang (Process Safety and Environmental Protection, 2026)

The impact of amendments on the microbial community response in green roof substrate layers - Wending Huang; Xinrui Huang; Mingyang Li; Junpeng Li; Jian Zhan; Hongwei Yang; Xin Li; Wei Liu; Na Yao; Wenjuan Wang; Shihao Zhang; Ya Wang; et al. (Journal of Environmental Management, 2026)

Mutant transcription factor CopR promotes LDB_RS05285 expression to suppress yogurt post-acidification and enhance texture stability - Wenhao Zhao; Xuemeng Fu; Dongyao Li; Qingqing Mu; Na Zhang; Yongsheng Sun; Miaoshu Wang; Hongtao Tian; Chen Li (Food Research International, 2026)

Hepatic cyp24a1 serves as a biomarker for diagnosing polystyrene microplastic exposure in Nile tilapia (Oreochromis niloticus) - Feilong Wang; Haiyan Xu; Xiaomeng Guo; Xiaolong Fan; Yuanyuan Li; Tiao Gao; Xin Xie; Na Guo; Fan Bai; Yixin Chen; Changle Zhao; Deshou Wang; et al. (Aquatic Toxicology, 2026)

Regulated cell death in endometrial diseases: from molecular mechanisms to targeted therapies - Duo Zi; Jing Sun; Na Zuo; Tingting Li; Junzhi Liang; Jia Hu; Zhijing Na; Hao Zhang; Lixia He; Da Li (Archives of Toxicology, 2026)

The single nucleotide polymorphism rs155787 on the autophagy gene of SQSTM1 is associated with silicosis susceptibility: A multi-stage study - Lijing Jiang; Fan Wang; Mingwei Huai; Wendi Zhang; Xiaofeng Chen; Chunping Li; Xinsheng Zhang; Bingchen Liu; Yao Su; Minjie Chu; Na Sun; Jiandong Jiao; et al. (Toxicology Letters, 2025)

Structure-based molecular design of fungicidal β-ketonitrile derivatives with biphenyl moiety as novel succinate dehydrogenase inhibitors - Cong Zhou; Ziye Cao; Li Sun; Na Zhai; Liangliang Cheng; Zheyi Feng; Zhong Li; Xuhong Qian; Jiagao Cheng (Pesticide Biochemistry and Physiology, 2025)

Impacts of gluten protein characteristics on the cracking behavior of dumpling wrappers during freeze-thaw cycles - Li-qin Tang; Xiaohong Sun; Xiao-Na Guo; Ke-Xue Zhu (Food Chemistry, 2025)

Targeted-nanoformulation of cannabidiol attenuates endothelial injury and platelet hyperactivation for combating silicosis - Sirong Chang; Yue Sun; Wenyue Zhang; Yi Guo; Huning Zhang; Nan Li; Ran An; Mengsi Xiao; Siwei Zou; Na Zhang; Kai Wang; Anning Yang; et al. (Chemical Engineering Journal, 2025)

New uses for old drugs: Targeted paroxetine-loaded liposomes for effective inhibition of cardiac fibrosis - Yang An; Ge Sun; Zhenzhen Dong; Yang Liu; Yubiao Huang; Xiaoyu Cheng; Wentao Zheng; Jiarui Du; Na Li; Yinlong Zhang; Chengzhi Yang (Chemical Engineering Journal, 2025)

Lignin nanoparticles mediated self-adhesive and conductive hydrogel electrolytes for high-performance flexible supercapacitors - Jiabin Han; Yuxin Song; Jiangbo Li; Bing Wang; Jian Zhang; Shuyi Li; Xingwen Wang; Na Li; Xueru Sheng; Haiqiang Shi; Changyou Shao; Runcang Sun (Chemical Engineering Journal, 2025)

Novel insights into the effect of sTIM-3 on NLRP3 inflammasome via interacting with ASC - Xiaodi Zhang; Na Han; Ziqing Xu; Zheng Tong; Xiaolei Ren; Yang Sun; Chunyang Li; Xuetian Yue; Zhuanchang Wu; Xiaohong Liang; Chunhong Ma; Pin Wang; et al. (Inflammation Research, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Topographic differences in EEG microstates: distinguishing juvenile myoclonic epilepsy from frontal lobe epilepsy - Ying Li; Lidao Xu; Yibo Zhao; Mingxian Meng; Yanan Chen; Bin Wang; Beijia Cui; Jin Liu; Jiuyan Han; Na Wang; Ting Zhao; Lei Sun; et al. (Cognitive Neurodynamics, 2025)

Synergistic electromagnetic and chemical enhancements in Al/C3N4/Ag@C for Raman-based chlortetracycline sensing - Jingyi Sun; Lujie Li; Tingting Zhang; Na Jiang; Zishan Guo; Congying Li; Weihua Li; Xianhuai Huang; Yan Li; Rui Lu (Analytica Chimica Acta, 2025)

Comparison of Muscle Texture Characteristics and Nutritional Composition Between Gene-Edited Intermuscular-Bone-Free Crucian Carp and Other Varieties - Huijie Zhou; Zhipeng Sun; Tan Zhang; Tingting Zhang; Ting Yan; Huan Xu; Mingliang Wei; Yashan Yin; Na Li; Youyi Kuang; Guangxiang Tong (Fishes, 2025)
The intermuscular-bone-free crucian carp (Carassius auratus, WUCI), developed through CRISPR/Cas9-mediated bmp6a and bmp6b knockout, offers advantages in consumer acceptance and processing efficiency. However, its effects on muscle texture and nutritional quality have not been fully elucidated. In this study, we compared the F3 generation of WUCI with its sibling wild-type crucian carp (Carassius auratus, WT), Songpu silver crucian carp (Carassius gibelio var. Songpu, SPYJ), and Fangzheng silver crucian carp (Carassius gibelio var. Fangzheng, FZYJ), focusing on muscle texture characteristics and nutritional attributes. WUCI exhibited significantly higher shear force but lower hardness than most comparison groups, with no substantial differences in muscle fiber morphology. Amino acid profiles were similar among all groups. WUCI showed lower crude fat content than WT but higher than FZYJ, and comparable levels of polyunsaturated fatty acids (PUFA), n-3 fatty acids, docosahexaenoic acid (DHA), and eicosapentaenoic acid (EPA) to WT and SPYJ. These findings indicate that the knockout of bmp6a and bmp6b does not alter muscle mass in crucian carp, supporting the potential of WUCI for commercial adoption as a gene-edited consumer-oriented fish product.

Elucidating the material basis and therapeutic mechanisms of Shaoma Zhijing granules for tourette syndrome by UPLC/Q-TOF-MS and multiple models - Qian Zhao; Xin-Xin Xu; Jin-Na Yang; Li-Juan Pei; Zhou-Yi Xie; Wen-Jia Wang; Jing-Xuan Fu; Zhao-Hui Song; He Sun; Kai-Jing Yan; Hui Wang; Yun-Hui Hu (Metabolic Brain Disease, 2025)

Matrine as a potent inhibitor of canine mammary tumors: Insights from network pharmacology, molecular docking, molecular dynamics and in vitro analysis - Fida Noor; Wenwen Ding; Na Sun; Panpan Sun; Huizhen Yang; Hua Zhang; Kuohai Fan; Wei Yin; Zhenbiao Zhang; Yaogui Sun; Jianzhong Wang; Jia Zhong; et al. (Veterinary Immunology and Immunopathology, 2025)

Newly discovered Late Paleolithic sites in the southeastern margin of the Badain Jaran Desert, northwest China - Lu Teng; Xuefeng Sun; Hui Liu; Na Zhao; Shuangwen Yi; Feng Li; Xiaoqi Guo; Yuan Yao; Yinghua Wang; Christopher J. Bae; Huayu Lu (Quaternary Science Reviews, 2025)

Effect of shrubs on soil microbial abundance and fungi-to-bacteria ratio depends on grazing conditions in semiarid grasslands - Le Li; Jiahui Liu; Jinsong Wang; Yunxiang Jin; Yu Sun; Jingmin Zhang; Na Zhu; Xu Wang; Dawei Xu; Yuhong Luo; Yufan Bao; Nuo Xu; et al. (Plant and Soil, 2025)

Wuhapuella caenivorax gen. nov., sp. nov., a Novel Member of the Family Weeksellaceae, a Flocculent Bacteria Isolated from an Urban Sewage Treatment Plant - Yangyang Sun; Qianzhi Wang; Shunda Qiu; Changcui Chen; Siqi Wu; Na Gao; Han Chen; Jun Yu; Chunlei Yang; Hao Li; Shijie Bai; Dongru Qiu; et al. (Current Microbiology, 2025)

Returning low C/N crop straw to the paddy field can achieve the dual benefits of reduced methane emissions and enhanced yield stability - Chuanhai Shu; Binbin Liu; Yu Li; Qiqi Chen; Leilei Li; Yuanqing Shi; Hongkun Xie; Zhonglin Wang; Qin Liao; Qingyue Cheng; Feijie Li; Na Li; et al. (Agriculture, Ecosystems & Environment, 2025)

A sliding window method considering image shadow to detect Mars rock from MRO HiRISE datasets - Na Sun; Yongjiu Feng; Xiaohua Tong; Pengshuo Li; Rong Wang; Yuhao Wang; Yuze Cao; Zilong Cao; Xiong Xu; Yusheng Xu; Shijie Liu (Planetary and Space Science, 2025)

Heteroaggregation between polystyrene micro(nano)plastics and dibutyl phthalate mediates toxicity reduction in macroalgae: Physiological and transcriptomic evidence from Gracilariopsis lemaneiformis - Yuanxia Li; Xiaoqian Zhang; Nianjun Xu; Mingze Chen; Wenting Tang; Na Zhou; Ting Zeng; Xue Sun; Zeming Zhang (Journal of Hazardous Materials, 2025)

Systematic experiments and a multi-criteria assessment framework to validate amendments-enhanced agglomerated matrix layer for green roof stormwater and pollutant control - Wending Huang; Yimi Huang; Wuhu Guo; Shaoye Du; Junpeng Li; Jian Zhan; Xin Li; Yuxin Li; Yinglong Shen; Ya Wang; Yanqi Liu; Yuejin Chen; et al. (Journal of Cleaner Production, 2025)

Characterization and efficacy of α-glucosidase inhibitory peptides from enzymatically hydrolyzed Peanut meal - Sen Zhou; Zhiran Zhang; Shengxin Li; Mengkai Liu; Ziyan Zhang; Na Wang; Jie Sun (Food Research International, 2025)

Investigating the effect of MAG/(NaPO3)x on the physicochemical and structural properties of rice starch-protein rice and improving the mechanism in each zone during the extrusion process - Li-shuang Wang; Jia-Sun; Jin-hui Jia; Jin-jie Huo; Yu-min Duan; Na-Wang; Xiao-shuai Yu; Zhi-gang Xiao; Ying Wang; Xiao-ling Tian (Food Structure, 2025)

Engineered apoferritin-coumarin nanosensor for hyper-sensitive in vivo tracking of plant isoprene emissions - Xuejia Sun; Tingxi Han; Jiaxing Li; Qijun Sun; Chenglin Su; Shuang Cao; Boyuan Qiao; Jiating Xu; Na Niu; Ligang Chen (Chemical Engineering Journal, 2025)

Diagnosing ozone formation regimes in Shandong province, China (2019–2023): Implications for volatile organic compounds control policies during the warm season and COVID-19 lockdowns - Lei Sun; Yetong Ma; Yichao Gai; Chuanyong Zhu; Zhenguo Liu; Renqiang Li; Chen Wang; Baolin Wang; Na Yang; Guihuan Yan; Chongqing Xu (Atmospheric Environment, 2025)

Sodium dehydroacetate induces porcine oocyte toxicity by inhibiting TCA cycle activity and mitochondrial function, with nicotinamide mononucleotide as a potential protective agent - Na Li; Yu Li; Guangjun Huang; Hongyu Sun; Jiaqi Wu; Qian Gao; Zhaokang Cui; Yilong Miao (Food and Chemical Toxicology, 2025)

Constructing nitrogen-doped porous organic polymer- supported single-atom cobalt catalysts for highly efficient hydroformylation of internal olefins - Yuqing Wang; Miao Jiang; Na Liu; Tian Tian; Changdao Li; Zhao Sun; Gewen Yu; Yanming Wang; Wenxiu He; Jian Ding; Li Yan; Yunjie Ding (Chemical Engineering Journal, 2025)

A novel flexible composite solid electrolyte based on 3D network structural inorganic Si-Zr-O-C fiber film - Amin Chen; Na Li; Chenxu Sun; Yanmin Qin; Luyao Qi; Huipei Zhang; Haifeng Bao (Chemical Engineering Journal, 2025)

Plant-insect interaction from the Middle Jurassic Haifanggou Formaton in Huludao, western Liaoning and its geological implications - Yuling Na; Tao Li; Yunfeng Li; Chunlin Sun; Xiao Shi; Xuemei Li (Palaeobiodiversity and Palaeoenvironments, 2025)

A strain of Rickettsia induces thelytoky in Anastatus gansuensis via maternal transmission - Run-Na Gong; Yong-Ming Chen; Jun-Bo Luan; Chen-Yi Li; Xiang Sun; Haneef Tariq; Lian-Sheng Zang (Journal of Pest Science, 2025)

Berberine attenuates the expression of NLRP3 and downstream inflammasome effectors in diabetic retinopathy - Na Li; Ji-Lin Chen; Yi-Jian Sun; Jia-Fan Sun; Ting-Hua Wang; Amy Yi Hsan Saik; Alan Han-Kiat Ong (Journal of Natural Medicines, 2025)

Machine learning based prediction by PlantCdMiner and experimental validation of cadmium-responsive genes in plants - Chaoqun Xu; Ling Sun; Lu-Dan Zhang; Ze-Jun Guo; Ji-Cheng Wang; Li-Han Zhuang; Dong-Na Ma; Ling-Yu Song; Jing Li; Qian-Su Ding; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2025)

Simultaneous determination of 16 herbicides in Procambarus clarkii - Na Li; Aiying Wang; Aijing Chen; Mengmeng Wu; Hongcai Liu; Yanyan Yang; Chao Wang; Dong Sun (Food Chemistry, 2025)

In situ construction of an organic/metal bridging interface toward zinc metal anode with ultra-long cycle life of 5000 h - Zhe Gong; Han Yu; Zhuo Li; Chenyi Yang; Feifei Gao; Pengfei Wang; Na Sun; Mingdong Zhou; Kai Zhu; Yaguang Sun (Chemical Engineering Journal, 2025)

Breaking genetic linkage barriers to improve brown planthopper resistance and grain yield in japonica rice - Wenhui Wang; Jun He; Yunlong Wang; Na Li; Quanguang Sun; Menglong Zhang; Qi Li; Haosen Xu; Kun Shao; Shihao Zhang; Shijia Liu; Liangming Chen; et al. (Theoretical and Applied Genetics, 2025)

Duplication and Functional Diversification of ANP3-Like Genes (MAPKKKs) in Rosaceae - Yibo Sun; Fupeng Bian; Taishuai Cui; Tiansi Fu; Li Zhang; Na Gao; Qian Zhang; Muhammad Irfan; Xiaojia Zhang; Lijing Chen (Journal of Plant Growth Regulation, 2025)

Fermented Chinese herbal medicines combined with probiotics promote growth of fattening lambs under heat stress by modulating rumen mucosal barrier functions - Shoupei Zhao; Xinsheng Sun; Na Zhao; Hongwei Zhang; Gaofu Wang; Lu Zhang; Yuqing Liu; Haitong Yang; Jianjie Li; Jia Zhou; Yuhong Gao (Animal Feed Science and Technology, 2025)

A novel Zn2+ probe for fluorescent monitoring of drug and E6/E7 protein interaction in living cells - Zhenzhen Xie; Lan Yu; Zuoping Li; Na Zhao; Shiwan You; Zhihao Zhao; Jindi Dou; Xiling Deng; Shiguo Sun (Analytica Chimica Acta, 2025)

A portable point-of-care testing platform for rapid and sensitive miRNA-21 detection for heart failure diagnosis - Qian Kai Lin; Wen Qing Sun; Bo Zhang; Qiao Ling; Yan Qian; Cheng Zhi Huang; Chun Mei Li; Na Wang (Analytica Chimica Acta, 2025)

Multi-Parameter Analysis of Stress Accumulation and Evolution Prior to the 2020 Guye MS5.1 Earthquake, North China: Insights from Apparent Stress, b-value, and Focal Mechanism Consistency - Xu-dong Ma; Lei Guo; Li-na Sun; Yi Zhou; Zhi-hua Ding (Applied Geophysics, 2025)

Effects of combination of UV-B irradiation and drying on the physicochemical properties of key components and processing quality of germinated whole wheat flour - Ting Wei; Wentong Liu; Jiahao Huang; Na Ji; Qingjie Sun; Man Li; Meng Ma; Fengwei Xie (Journal of Cereal Science, 2025)

Investigating the differences in β-Cyclodextrin derivatives / Hyperoside inclusion complexes: Dissolution properties, thermal stability, and antioxidant activity - Peiran Liu; Na Gan; Qinhong Li; Zhen Zeng; Jie Zhong; Xinhui Wang; Yanxia Sun; Di Wu (Food Chemistry, 2025)

Sous-vide cooking as a promising approach for developing high-quality salt pan shrimp products - Chenqi Li; Songyi Lin; Tingjia Chen; Shuo Wang; Xixin Qian; Dong Chen; Ruming Wang; Na Sun (Food Chemistry, 2025)

Surfactant charge tuning alters casein micelle structure and complexation behavior - Liying Yang; Mengjia Chen; Yunyan Luo; Shuyuan Yang; Na Li; Yang Sun (Food Hydrocolloids, 2025)

Genetic deletion of microRNA-15a/16-1 in pericytes stimulates cerebral angiogenesis and promotes functional recovery after ischemic stroke - Ping Sun; Yang Xu; Tianqing Xiong; Shun Li; Na Qiu; Chao Zhou; Jiefei Wang; Alexander Chang; Uma R. Chandran; Ke-Jie Yin (Angiogenesis, 2025)

UV-B stress reshapes root-associated microbial communities and networks, driven by host plant resistance - Chuanji Zhang; Na Gao; Xiaofan Na; Kaile Li; Meiyun Pu; Hao Sun; Yanfang Song; Tong Peng; Panshuai Fei; Junjie Li; Zhenyu Cheng; Xiaoqi He; et al. (Soil Biology and Biochemistry, 2025)

Microwave heating as a promising alternative to traditional two-stage heating in the production of sodium-reduced shrimp surimi - Xixin Qian; Songyi Lin; Shuang Li; Shuo Wang; Chenqi Li; Dong Chen; Na Sun (Innovative Food Science & Emerging Technologies, 2025)

Unveiling fungal degradation pathways for polyurethane and polyethylene through enrichment cultures and metabolic analysis - Eyalira Jacob Okal; Jie Zhou; Yanfei Wu; Tingfang Zhong; Yue Tang; Zhengyu Sun; Ruifang Xu; Yuwei Hu; Na Hu; Jingxian Li; Samantha C. Karunarathna; Peter E. Mortimer; et al. (International Biodeterioration & Biodegradation, 2025)

Structure identification and biological activity of a novel sulfated glycosaminoglycan-like polysaccharide from Sepia recurvirostra ink - Nanqi Cheng; Na Gao; Pin Wang; Yujun Ma; Pengfei Li; Xiaolu Wu; Jiaying Sun; Yulan Dai; Jinhua Zhao (Carbohydrate Polymers, 2025)

Antimicrobial Peptides: Classification, Mechanism, and Application in Plant Disease Resistance - Yuan-Zhen Wu; Jin Wang; Ying-Hui Hu; Qi-Shuo Sun; Rui Geng; Li-Na Ding (Probiotics and Antimicrobial Proteins, 2025)

Long Non-Coding RNAs: Crucial Regulators in Alzheimer’s Disease Pathogenesis and Prospects for Precision Medicine - Chenbo Yang; Yiwei Li; Chao Chen; Zexin Sun; Enjie Liu; Na Wei; Xiaonan Liu; Jiao Shu; Na Zhao; Miaomiao Sun (Molecular Neurobiology, 2025)

Co-variation of Host Gene Expression and Gut Microbiome in Intestine-Specific Spp1 Conditional Knockout Mice - Na Li; Guangqi Gao; Tao Zhang; Chunyan Zhao; Yue Zhao; Yong Zhang; Zhihong Sun (Current Microbiology, 2025)

Spatial and temporal distribution, fate, and potential health risks of microplastics in urban indoor air - Liyuan Peng; Na Zheng; Qirui An; Xiaoqian Li; Siyu Sun; Yunyang Li; Jingze Yu; Fan Shao; Yingxi Qiu; Shuyue Zhang (Gondwana Research, 2025)

Thermal stability design of cable-net structure for mesh reflector antennas - Zihan Sun; Yiduo Quan; Naigang Hu; Na Li; Yiqun Zhang (Advances in Space Research, 2025)

Depositional age and source material of banded iron formations in the Western Shandong Province, North China Craton: Constraints from geochemistry, zircon U Pb geochronology and Sm Nd isotope composition - Yan Zhang; Wei Xie; Dapeng Li; Qiang Liu; Yuqin Sun; Chenxi Zhang; Ke Geng; Pengfei Wei; Chao Zhang; Na Cai (Journal of Geochemical Exploration, 2025)

Modified attapulgite loaded nanoscale zero-valent iron for Cr(VI) removal in three-dimensional electrode system: Performance and mechanism - Zhi Li; XiaoMei Zhu; Xueru Wei; HanQi Zhang; Na Cao; XinDi Shi; Bing Sun (Journal of Environmental Chemical Engineering, 2025)

Development of sensitive and rapid immunoassays for Moniliformin (MON) detection based on nanomaterials labeled monoclonal antibodies - Lakshani Madushika; Yongming Huang; Menghan Sun; Yuxuan Liu; Linfang Lu; Xiaoli Li; Na Li; Kang Jiang; Sumei Ling; Shihua Wang (Food Chemistry, 2025)

Identification and validation of a major QTL, QFhb-6AL, for Fusarium head blight resistance on chromosome 6AL in wheat - Zhenzhen Zhu; Xuecheng Zhu; Na Zhang; Wenxi Wang; Jilu Liu; Fuping Zhang; Xiaomeng Ren; Yanpeng Ding; Fangyao Sun; Xi He; Sijia Hu; Xiuhua Li; et al. (Theoretical and Applied Genetics, 2025)

Characterization and Assessment of Sheep-Origin Probiotic Bacillus licheniformis B63 Strain for Potential Use in Intestinal Health and Disease - Meng Hou; Yabin Lu; Mengjun Ye; Na Li; Yawei Sun; Gang Yao; Jinquan Wang; Fangfang Yin; Qimin Peng; Sheng Jia; Rui Shi; Xuxiang Wang (Probiotics and Antimicrobial Proteins, 2025)

Review on recent advancements in understanding acetylsalicylic acid-induced gastrointestinal injury: mechanisms, medication, and dosage refinement - Jiahui Zhou; Na Li; Xinzhong Li; Jingxue Ye; Min Wang; Guibo Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Grazing exclusion changes the complexity and stability but not the α-diversity of the microbial community in a desert steppe - Fengqin Yuan; Xuebao Xu; Zhenpeng Liu; Rula Sa; Chongzhi Sun; Jia Liu; Na Li; Yujuan Zhang; Tongrui Zhang; Tingting Xing; Jie Ren; Shiming Tang; et al. (Applied Soil Ecology, 2025)

N-doped carbon nanotubes encapsulated Ni3ZnC0.7 nanoparticles catalyst for peroxymonosulfate activation: Heterojunction structure and N-doping enhance electron transfer capability - Qihao Sun; Huiyuan Deng; Na Zhao; Junjie You; Zhicheng Pan; Bo Xing; Yuling Ye; Bo Lai; Xinye Yang; Xinjie Wang; Yunhui Lu; Jian Li; et al. (Chemosphere, 2025)

Nicotinamide mononucleotide enhances the developmental potential of mouse early embryos exposed to perfluorooctanoic acid - Hanwen Zhang; Yu Li; Na Li; Yilong Miao; Shaochen Sun; Ling Gu; Bo Xiong (Reproductive Toxicology, 2025)

Sesquiterpenoids from Inula britannica and their potential mechanism for immunomodulation - Hui-Lin Zhang; Na Wang; Xu-Liu Shi; Miao-Miao Wang; Qi-Meng Zhu; Jing Chang; Yan-Li Feng; Juan Zhang; Feng Qiu; Cheng-Peng Sun (Phytochemistry, 2025)

Metabolic landscape of human alveolar type II epithelial cells undergoing epithelial-mesenchymal transition induced directly by silica exposure - Jin Sun; Na Zhao; Ruijia Zhang; Yizheng Li; Tiantian Yu; Qiying Nong; Li Lin; Xubin Yang; Tiangang Luan; Baowei Chen; Yongshun Huang (Journal of Environmental Sciences, 2025)

Characterization of microplastic distribution, sources and potential ecological risk assessment of domestic sewage from ships - Na Lu; Qing Su; Yuxia Li; Ling Qu; Lingna Kong; Jiayi Cheng; Chao Wang; Jian Sun; Jianbo Han; Xiaomeng Wang (Environmental Research, 2025)

How to promote sustainable recycling of plastic packaging waste? A study combining machine learning with gaming theory - Shuhan Yang; Ruyin Long; Hong Chen; Jingwen Na; Qingqing Sun; Ting Yue; Qianwen Li; Xinru Wang; Wanqi Ma; Mark Goh (Environmental Impact Assessment Review, 2025)

Robust localization and tracking control of high-clearance robot system servicing high-throughput wheat phenotyping - Qinghan Hu; Zhengqiang Fan; Xihai Zhang; Na Sun; Xuefeng Li; Quan Qiu (Computers and Electronics in Agriculture, 2025)

A novel 0D/2D heterojunction Bi2Sn2O7/BiOCOOH with BiOCOOH nanosheets as support for the boosted photodegradation of tetracycline: The role of BiOCOOH in the photogenerated electron transfer - Shuo Han; Fangyan Chen; Yubin Tang; Wenqian Sun; Yanhua Song; Kaiwen Zhang; Na Li (Journal of Environmental Chemical Engineering, 2025)

Decoding the textural deterioration of ready-to-eat shrimp: Insights from dynamic myofibrillar protein changes during thermal sterilization - Shuo Wang; Songyi Lin; Shuang Li; Xixin Qian; Chenqi Li; Na Sun (Food Research International, 2025)

Effects of sodium chloride on the textural attributes, rheological properties, microstructure, and 3D printing performance of rice starch-curdlan composite gel - Weixian Li; Kangning Zhang; Yang Qin; Man Li; Hongyan Li; Minqiang Guo; Tongcheng Xu; Qingjie Sun; Na Ji; Fengwei Xie (Food Chemistry, 2025)

Novel one-step method to construct gellan gum-zein core-shell structured starch beads for regulating starch digestion - Zhiwei Lin; Weixian Li; Chengcheng Zhang; Linjie Zhan; Xiaoyang He; Yang Qin; Qingjie Sun; Na Ji (Food Chemistry, 2025)

Antifungal activities of Pediococcus pentosaceus LWQ1 and Lactiplantibacillus plantarum LWQ17 isolated from sourdough and their efficacies on preventing spoilage of Chinese steamed bread - Xueying Wu; Yongxin Liu; Zhengli Guo; Na Ji; Qingjie Sun; Tongjie Liu; Yang Li (Food Control, 2025)

N-doped biochar supported Ni-Co alloy catalyst for efficient hydrocracking of enzymatic hydrolysis lignin to monophenols in water - Zifan Wu; Yacong Deng; Fengyu Tian; Yidi Wang; Na Fan; Guangzheng Sun; Yichuan Li; Yuan Pan; Bin Liu; Bin Dong; Han Hu; Yongming Chai (Chemical Engineering Journal, 2025)

Effective enhancement of ramie anaerobic continuous flow degumming by chitosan and its microbiological mechanism - Xuehui Xie; Yiting Qin; Haonan Mo; Zhuoyu Zhao; Yuling Li; Yanxue Ma; Yao Sun; Dongyang Li; Ziyi Wu; Na Liu; Qingyun Zhang; Xiaoguang Chen (Bioresource Technology, 2025)

Chemical constituents from Silene firma and their chemotaxonomic significance - Liang Sun; Jinling Zhang; Na Li; Changhao Zhang (Biochemical Systematics and Ecology, 2025)

Ferroptosis-Related Gene Signatures in Epilepsy: Diagnostic and Immune Insights - Xueying Li; Lei Wu; Linlin Sun; Han Liu; Xuezhu Qiao; Na Mi; Shi Yan; Xinyu Zhang; Kun Wang; Pusheng Quan; Fan Yang; Lifen Yao (Molecular Neurobiology, 2025)

AMPK activation by dietary acadesine improves fillet texture in large yellow croaker (Larimichthys crocea) fed a linseed oil-based diet - Shengdi Chen; Zihan Sun; Ningning Liu; Chenbin Yang; Na Li; Lu Li; Chaoqing Wei; Binlun Yan; Huan Gao; Peng Tan; Hua Mu (Aquaculture, 2025)

Evaluation of water environmental capacity in a northern river-reservoir continuum using environmental fluid dynamics code - Qingqing Sun; Huanlian Ren; Mohd Aadil Bhat; Na Liu; Zhaolun Li; Zechao Li; Qiliang Cheng; Yimeng Ren; Ning Yang; Zhuoni Ma (Science of The Total Environment, 2025)

Benzofurans and dibenzofurans from galls on twigs of the endangered Chinese endemic tree Parrotia subaequalis and their inhibitory properties against Staphylococcus aureus and ATP-citrate lyase - Peng-Jun Zhou; Xi-Ying Wu; Ze-Yu Zhao; Yi Zang; Zhong-Shuai Sun; Yue-Ling Li; Na Li; Juan Xiong; Yeun-Mun Choo; Ze-Xin Jin; Jia Li; Jin-Feng Hu (Phytochemistry, 2025)

Investigation of an outbreak of hepatitis E virus 4d reveals the importance of good kitchen hygiene - Yuan Sun; Yulou Sun; Sisi Tan; Na Li; Kui Wang; Xinxin Zhang; Bingyang Li; Feng Hao; Cuiqun Sun; Peng Chen (International Journal of Food Microbiology, 2025)

Establishment of highly sensitive lateral flow immunochromatographic strips for quinclorac detection utilizing signal amplification nanoparticles - Yongming Huang; Yuxuan Liu; Menghan Sun; Linfang Lu; Xiaoli Li; Kang Jiang; Na Li; Sumei Ling; Shihua Wang (Food Chemistry, 2025)

Joint action of six-component mixtures based on concentration response curves morphological parameter in acute and long-term toxicity assay - Yujiao Zhang; Yajiao Li; Na Wang; Xiaoyan Ma; Jiajing Sun; Xiaochang Wang; Jiaxuan Wang (Environmental Toxicology and Pharmacology, 2025)

Polystyrene nanoplastics induce apoptosis, histopathological damage, and glutathione metabolism disorder in the intestine of juvenile East Asian river prawns (Macrobrachium nipponense) - Yiming Li; Yucong Ye; Xiaoyi Zhu; Siwen Li; Na Rihan; Zongli Yao; Zhen Sun; Pengcheng Gao; Yunlong Zhao; Qifang Lai (Science of The Total Environment, 2024)

Meta-analysis: Global patterns and drivers of denitrification, anammox and DNRA rates in wetland and marine ecosystems - Jiaqi Lun; Wenxi Zhou; Mengyue Sun; Na Li; Wenchong Shi; Zheng Gao; Mingcong Li (Science of The Total Environment, 2024)

Intimate microbe-water-mineral interactions mediate alkalization in the pyroxene-rich iron ore mines in Panxi area, Southwest China - Yu He; Yongzhe Li; Yue Pan; Jianying Shang; Weimin Sun; Meng Wang; Hao Fan; Robert A. Sanford; Na Wei; Shuming Peng; Daihong Xie; Weiguang Zhang; et al. (Journal of Hazardous Materials, 2024)

Tissue-specific distribution and fatty acid content of PFAS in the northern Bohai Sea fish: Risk-benefit assessment of legacy PFAS and emerging alternatives - Zhifei Xiu; Na Zheng; Qirui An; Changcheng Chen; Qiuyan Lin; Xiaoqian Li; Sujing Wang; Liyuan Peng; Yunyang Li; Huicheng Zhu; Siyu Sun; Shuai Wang (Journal of Hazardous Materials, 2024)

Contribution for lake phytoplankton community succession under multi-source artificial hydrological regulation - Bowen Sun; Na Li; Guoyu Wang; Xueping Gao; Xushen Zhou; Fanqing Kong (Journal of Environmental Management, 2024)

Effect of probiotic fermentation on the extraction rate and bioactivity of plant-based polysaccharides: A review - Zichao Wang; Yi Zheng; Yibo Dai; Rongchao Yang; Renyong Zhao; Gangchun Sun; Wen-Wen Zhou; Shouai Feng; Yingjie Feng; Na Li; Jinchu Yang; Huiru Zhang; et al. (Innovative Food Science & Emerging Technologies, 2024)

Modulation of the receptor for advanced glycation end products pathway by natural polyphenols: A therapeutic approach to neurodegenerative diseases - Yinghao Wei; Yanqing Zhang; Jie Sun; Wei Li; Xiaotong Zhao; Na Tian; Yuxin Cao; Junbo Xie (Food Bioscience, 2024)

Atmosphere-driven oriental regulation of Ru valence for boosting alkaline water electrolysis - Na Xu; Man-Man Li; Hai-Yi Sun; Guodong Li; Xin Wen; Denghao Ouyang; Chun-Ying Liu; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Identification of a novel intronic variant of ATP6V0A2 in a Han-Chinese family with cutis laxa - Ying Zhang; Mei Sun; Na Li; Yiran Zhao; Fang Zhang; Jianbo Shu; Yang Liu; Chunquan Cai (Molecular Biology Reports, 2024)

Evolutionary and functional conservation of IRF7 in the Tibetan frog Nanorana parkeri - Qing Wang; Bo Li; Xin Na Sun; Zhen Gan (Molecular Biology Reports, 2024)

The potential role of hippo pathway effector yap1/yap1b in female-biased sexual size dimorphism of Chinese tongue sole (Cynoglossus semilaevis) - Jiaqi Mai; Yuqi Sun; Xihong Li; Ying Zhu; Wenteng Xu; Zhangfan Chen; Qi Zhang; Jiacheng Wang; Na Wang (Aquaculture, 2024)

Improving hydrological modeling to close the gap between elevated CO2 concentration and crop response: Implications for water resources - Na Wen; Yiwen Han; Junyu Qi; Gary W. Marek; Danfeng Sun; Puyu Feng; Raghavan Srinivasan; De Li Liu; Yong Chen (Water Research, 2024)

Proteasome inhibition induces apoptosis through simultaneous inactivation of MCL-1/BCL-XL by NOXA independent of CHOP and JNK pathways - Wenjuan Chen; Mengning Sun; Yi Sun; Qinglan Yang; Hui Gao; Li Li; Rongrong Fu; Na Dong (Toxicology, 2024)

Acne-related UVA-induced facial fluorescence: An exploratory study from physiological properties to tissue structure information - Xing Ren; Yanan Sun; Yuxin Zhang; Na Zhou; Yunong Wang; Lishuang Li; Xinyu Gao; Yuman Ma; Xianyu Li; Zhe Shu; Honghui He; Yi Wang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Comparative analysis of anaerobic degumming effects on different bast fibers from the angle of enzyme activity and microbial community structure - Yiting Qin; Xuehui Xie; Haonan Mo; Yuling Li; Xiaoguang Chen; Yanxue Ma; Zhuoyu Zhao; Hangmi Zheng; Yao Sun; Dongyang Li; Ziyi Wu; Na Liu; et al. (Journal of Cleaner Production, 2024)

Evaluation of the texture characteristics and taste of shrimp surimi with partial replacement of NaCl by non‑sodium metal salts - Xixin Qian; Songyi Lin; Tingjia Chen; Shuang Li; Shuo Wang; Chenqi Li; Ruming Wang; Na Sun (Food Chemistry, 2024)

Exploring the role of the thick and dense calcium alginate shell on the anti-digestibility mechanism of corn starch/carboxymethyl cellulose/calcium alginate liquid-core beads prepared by reverse spherification - Jinling Zou; Kangning Zhang; Weixian Li; Yang Qin; Qingjie Sun; Na Ji; Fengwei Xie (Food Hydrocolloids, 2024)

A nanozyme-based drug delivery system to amplify ferroptosis via MET inhibition and photodynamic therapy - Mengran Xu; Fuxuan Lai; Hu Liu; Delin Hu; Yexiang Sun; Fenfen Li; Min Sun; Na Lv; Bensheng Qiu; Yueyin Pan; Yi Hu (Chemical Engineering Journal, 2024)

Effect of powder activated carbon (PAC) addition on the performance of anaerobic dynamic membrane bioreactor (AnDMBR): Stratification analysis of dynamic membrane characteristics - Yuqi Sun; Qingyang Guo; Wenkai Rao; Na Li; Yuxin Bai; Jian Zhang; Shuang Liang (Chemical Engineering Journal, 2024)

Phthalates on indoor surfaces and associated exposure via surface touch behavior: Observation in university dormitories and its implications - Fangzhou Yuan; Yu Sun; Na Li; Jianping Cao; Nan Zhang; Daniel Mmereki; Zhonghua Wei; Rui Chen; Jinyu Zhou; Yousheng Xu; Zhongming Bu (Building and Environment, 2024)

Investigating the Effects of Perampanel on Autophagy-mediated Regulation of GluA2 and PSD95 in Epilepsy - Dan Li; Na Sun; Yingying Guo; Shaoping Huang; Chunyan Yin; Yanfeng Xiao; Weijun Ma (Molecular Neurobiology, 2024)

Long-term changes of surface ozone and ozone sensitivity over the North China Plain based on 2015–2021 satellite retrievals - Chuanyong Zhu; Yichao Gai; Zhenguo Liu; Lei Sun; Siyuan Fu; Kun Liu; Leifeng Yang; Guang Pan; Baolin Wang; Chen Wang; Na Yang; Zhisheng Li; et al. (Air Quality, Atmosphere & Health, 2024)

A systematic review of decarbonization pathway and modeling conception in iron and steel industry at micro-, meso-, and macro-levels - Jingchao Sun; Hongming Na; Yuxing Yuan; Ziyang Qiu; Tao Du; Yingnan Li; Lei Zhang; Weichen Wang (Environmental Science and Pollution Research, 2024)

Fourteen-year field experiment reveals neutral effects of N and P deposition on abundance and stoichiometric traits of the earthworm Pontoscolex corethrurus in tropical plantations - Zhifeng Shen; Xin Wang; Faming Wang; Jian Li; Jing Sun; Xiaoming Zou; Yiqing Li; Suli Li; Na Wang; Shenglei Fu; Weixin Zhang (Soil Biology and Biochemistry, 2024)

Fine particulate matter components associated with exacerbated depressive symptoms among middle-aged and older adults in China - Haisheng Wu; Jiaqi Liu; Erica Conway; Na Zhan; Lishuang Zheng; Shengzhi Sun; Jinhui Li (Science of The Total Environment, 2024)

Space electric field impacts on softening and cell wall modification of strawberry during cold storage - Sun Xiyun; Tian Sihui; Li Bin; Zhang yunhe; Li Dongnan; Yang Na; Wang Yuehua; Yu Jumeng (Postharvest Biology and Technology, 2024)

κ-Carrageenan improves the gelation capacity of Antarctic krill myofibrillar proteins through covalent and noncovalent interactions - Shuang Li; Songyi Lin; Pengfei Jiang; Xixin Qian; Shuo Wang; Na Sun (Food Hydrocolloids, 2024)

Tailoring physicochemical properties of quaternized polystyrene-ethylene/butylene-styrene membrane for enhanced pervaporation desalination - Xinxin Sun; Na Li; Ziheng Wang; Weiyu Shen; Zongli Xie; Yilin Liu; Liwen Jin (Desalination, 2024)

Exploring mass transfer mechanisms in reverse osmosis membranes: A comparative study of SDM and DSPM-DE models - Fei Sun; Kun Li; Na Li; Jiulong Yin; Yuxuan Xue; Yutong Gu; Lei Qi; Meng Li; Yujian Yao; Xuan Zhang (Desalination, 2024)

Dynamic pathology and pathogen distribution of the yeast Metschnikowia bicuspidata in the Chinese mitten crab ( Eriocheir sinensis ) - Xinran Shi; Na Sun; Jiannan Liu; Senting Pu; Zhouling Chen; Dong Sheng; Kexin Hao; Xiaodong Li; Shigen Ye (Journal of Fish Diseases, 2024)
In this study, the “milky disease” model of Eriocheir sinhensis was constructed via intramuscular injection with the pathogenic yeast Metschnikowia bicuspidata . The dynamic pathological changes of E. sinensis after injection were elucidated with two staining methods (haemotoxylin‐eosin and alcian blue periodic acid‐Schiff) and fluorescence in situ hybridization technology. Anatomical observation revealed three stages of the “milky disease”: no clinical signs (1–4 days after infection), the appearance of signs of disease (5–7 days), and significant liquefaction (10 days). Histological observation also revealed three stages of the disease: yeast diffusion (1–2 days after infection), yeast slow development (3–4 days), and yeast rapid proliferation (5 days). And FISH technique was suitable for the early detection of infection with M. bicuspidata in E. sinensis . We found that M. bicuspidata spread to the whole body of the crab through the haemolymph and developed into fungal septicaemia. These results elucidate the systemic pathological characteristics of “milky disease” in E. sinensis and suggest the pathogenic mechanism of M. bicuspidata .

Novel Br-doped Bi2WO6 photocatalyst for high-efficiency removal of norfloxacin: mechanism and photocatalytic activity - Zhi Li; XiaoMei Zhu; ZhuoLing Chen; Na Cao; Hui Liu; Bing Sun (Environmental Science and Pollution Research, 2024)

Ti3C2 quantum dots-modified oxygen-vacancy-rich BiOBr hollow microspheres toward optimized photocatalytic performance - Tao Cheng; Zipeng Xing; Na Zhang; Peng Sun; Hui Peng; Zhenzi Li; Nan Wang; Wei Zhou (Chemosphere, 2024)

Chromene meroterpenoids from Rhododendron dauricum L. and their anti-inflammatory effects - Na Zhang; Yang Xu; Dejuan Sun; Yuxia Li; Hua Li; Lixia Chen (Phytochemistry, 2024)

Biochar with KMnO4-hematite modification promoted foxtail millet growth by alleviating soil Cd and Zn biotoxicity - Xirui Kang; Na Geng; Yaping Li; Wei He; Hui Wang; Hong Pan; Quangang Yang; Zhongchen Yang; Yajie Sun; Yanhong Lou; Yuping Zhuge (Journal of Hazardous Materials, 2024)

Enhanced immobilization of cadmium and lead in contaminated soil using calcium alginate-modified HAP biochar: Improvements in soil health and microbial diversity - Yining Ji; Na Zheng; Qirui An; Sujing Wang; Siyu Sun; Xiaoqian Li; Changcheng Chen; Shuhai Sun; Yifu Jiang (Environmental Pollution, 2024)

Relationship between resistivity and physical properties of seafloor sediments in the hydrate production test area of the South China Sea - Zhiwen Sun; Yiping Miao; Zhihan Fan; Xiaoshuai Song; Liang Xue; Na Zhu; Xianming Zhu; Xiaomeng Li; Yue Qiao; Zhongqiang Sun; Kai Li; Yanlong Li; et al. (Marine Georesources & Geotechnology, 2024)

Identification of Autophagy-Related Candidate Genes in the Early Diagnosis of Alzheimer’s Disease and Exploration of Potential Molecular Mechanisms - Jian Wang; Xinhua Huo; Huiqin Zhou; Huasheng Liu; Xiaofeng Li; Na Lu; Xuan Sun (Molecular Neurobiology, 2024)

Plasma Deoxycholic Acid Levels are Associated with Hemodynamic and Clinical Outcomes in Acute Pulmonary Embolism Patients - Na Sun; Yi-Qiang Chen; Yan-Sheng Chen; Lei Gao; Run-Wei Deng; Jing Huang; You-Li Fan; Xuan Gao; Bin-Feng Sun; Na-Na Dong; Bo Yu; Xia Gu; et al. (Cardiovascular Toxicology, 2024)

Pristimerin exhibits anti-cancer activity by inducing ER stress and AKT/GSK3β pathway through increasing intracellular ROS production in human esophageal cancer cells - Wei-Bin Hu; Yi-Ting Liu; Jing Li; Ying Wang; Xuan-Zi Sun; Ming-Yu Hua; Xue-Ting Liu; Bei-Na Hui (Toxicology in Vitro, 2024)

Antibiotic resistance of Escherichia coli isolated from food and clinical environment in China from 2001 to 2020 - Changzhen Liu; Shaojing Sun; Yan Sun; Xuli Li; Weimin Gu; Yi Luo; Na Wang; Qing Wang (Science of The Total Environment, 2024)

Association between residential greenness and incident delirium: A prospective cohort study in the UK Biobank - Qida He; Mengtong Sun; Yu Wang; Guoxian Li; Hanqing Zhao; Ze Ma; Zhaolong Feng; Tongxing Li; Qiang Han; Na Sun; Linyan Li; Yueping Shen (Science of The Total Environment, 2024)

Effects of different thermal sterilization conditions on the quality of ready-to-eat shrimp based on specific sterilization intensity - Shuo Wang; Songyi Lin; Shuang Li; Xixin Qian; Chenqi Li; Na Sun (Food Chemistry, 2024)

Steep oceanic DIC δ13C depth gradient during the Hirnantian Glaciation - Shengchao Yang; Junxuan Fan; Thomas J. Algeo; Graham A. Shields; Ying Zhou; Chao Li; Jitao Chen; Weiqiang Li; Na Li; Jian Cao; Linna Zhang; Zongyuan Sun; et al. (Earth-Science Reviews, 2024)

A review on intelligence of cellulose based materials - Zhanying Sun; Xin Wang; Haoran An; Shuang Liang; Na Li (Carbohydrate Polymers, 2024)

Spatiotemporal ozone concentration variations and their influencing factors in Zhejiang, China, 2018–2022: A geographically and temporally weighted regression - Yi Li; Qing Hou; Bingye Xu; Wenlong Zhao; Jinmei Ding; Lingling Jin; Qiaoli Zou; Xudong Tian; Shengchen Xu; Xin Sun; Na Chao (Atmospheric Pollution Research, 2024)

Astaxanthin Rescues Memory Impairments in Rats with Vascular Dementia by Protecting Against Neuronal Death in the Hippocampus - Na Wei; Luo-man Zhang; Jing-Jing Xu; Sheng-lei Li; Rui Xue; Sheng-li Ma; Cai Li; Miao-miao Sun; Kui-sheng Chen (NeuroMolecular Medicine, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Eco-friendly drinking straws: Navigating challenges and innovations - Yuanpu Liu; Na Li; Xuyang Zhang; Ting Wei; Meng Ma; Qingjie Sun; Man Li; Fengwei Xie (Trends in Food Science & Technology, 2024)

Effect of Lactobacillus fermentation on the structural feature, physicochemical property, and bioactivity of plant and fungal polysaccharides: A review - Zichao Wang; Yi Zheng; Xueyan Zhou; Xueqin Wang; Xirui Liu; Qiong Wang; Renyong Zhao; Minjie Gao; Zhitao Li; Yingjie Feng; Yongming Xu; Na Li; et al. (Trends in Food Science & Technology, 2024)

Impact of greening trends on biogenic volatile organic compound emissions in China from 1985 to 2022: Contributions of afforestation projects - Yichao Gai; Lei Sun; Siyuan Fu; Chuanyong Zhu; Changtong Zhu; Renqiang Li; Zhenguo Liu; Baolin Wang; Chen Wang; Na Yang; Juan Li; Chongqing Xu; et al. (Science of The Total Environment, 2024)

Carbazole-Based branched Poly(Aryl Piperidinium) membranes for Ultra-Stable anion exchange membrane fuel cells - Jiayao Yang; Jialin Zhao; Na Li; Yijia Lei; Jingyi Wu; Jian Gao; Shiyao Sun; Kuirong Feng; Yan Wang; Zhe Wang (Chemical Engineering Journal, 2024)

Air-water-fertilizer-coupling Drip Irrigation Facilitates Lettuce Growth by Shaping Rhizosphere Microbiome Associated with Soil Nutrient Cycling - Na Xu; Runya Yang; Zhenhua Zhang; Jinjin Zhu; Zhe Zhang; Yunfei Mao; Shanshan Li; Yajun Geng; Junna Sun (Journal of Soil Science and Plant Nutrition, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Clinically relevant immune subtypes based on alternative splicing landscape of immune-related genes for lung cancer advanced PPPM approach - Na Li; Wenshuang Jia; Jiahong Wang; Qianwen Shao; Xiaoxia Feng; Zhijun Li; Wenhao Sun; Ming Kang; Dongming Hu; Ligang Xing; Xianquan Zhan (EPMA Journal, 2024)

Antifungal mechanism of protocatechuic acid methyl ester against Botrytis cinerea in postharvest strawberry fruit - Shuzhi Yuan; Baogang Wang; Meng Wang; Minmin Sun; Xuanqi Wang; Xiaofei Li; Na Yang; Xiaodi Xu; Shufang Zheng; Qing Wang (Postharvest Biology and Technology, 2024)

Electroactive nanofibrous membrane with antibacterial and deodorizing properties for air filtration - Yuejie Dou; Na Wang; Shaohua Zhang; Caihong Sun; Jinmiao Chen; Zhenghai Qu; Aihua Cui; Jiwei Li (Journal of Hazardous Materials, 2024)

Exploration the interaction of cadmium and copper toxic effects in pakchoi (Brassica chinensis L) roots through combinatorial transcriptomic and weighted gene co-expression network analysis - Qirui An; Na Zheng; Yining Ji; Siyu Sun; Sujing Wang; Xiaoqian Li; Changcheng Chen; Ning Li; Jiamin Pan (Journal of Environmental Management, 2024)

Multiple stimulus responsive of a novel naphthalenediimide-based 2D alkaline-earth metal MOF material: Hydrochromism, amine-/acid-induced chromism and ionochromism as well as visual artificial film application - Rong Huo; Ting Zhang; Li Xian Sun; Li Na Zhao; Yong Heng Xing; Feng Ying Bai (Chemical Engineering Journal, 2024)

MicroRNA-322-5p targeting Smurf2 regulates the TGF-β/Smad pathway to protect cardiac function and inhibit myocardial infarction - Liping Guo; Ke Li; Yan Ma; Huaiming Niu; Jun Li; Xin Shao; Na Li; Yuehui Sun; Haixiong Wang (Human Cell, 2024)

Crosstalk between autophagy and inflammasomes in ricin-induced inflammatory injury - Shiji Zhang; Na Zhao; Suli Song; Yanchun Wang; Yan Wang; Chengbiao Sun; Mingxin Dong; Mengqi Huo; Na Xu; Wensen Liu; Guorui Li (Toxicology and Applied Pharmacology, 2024)

The effects of cadmium-copper stress on the accumulation of antibiotic-resistance genes in soil and pakchoi leaves - Jiamin Pan; Na Zheng; Qirui An; Yunyang Li; Siyu Sun; Sujing Wang; Yining Ji; Ning Li (Soil Biology and Biochemistry, 2024)

Copper nanoparticles encapsulated in zeolite 13X for highly selective hydrogenation of CO2 to methanol - Yingnan Li; Tao Du; Chuang Chen; He Jia; Jingchao Sun; Xin Fang; Yisong Wang; Hongming Na (Journal of Environmental Chemical Engineering, 2024)

Preparation of porous-structured flat potato starch noodles with gelatin for shortening cooking time - Yongdi Li; Zhongxiu Wang; Yang Qin; Na Ji; Liu Xiong; Qingjie Sun (Food Hydrocolloids, 2024)

Lignin/mesoporous hollow silica nanosphere thin film nanocomposite loose nanofiltration membrane for dye/salt separation - Qiang Li; Wenge Sun; Bin Shang; Na Zhang; Li Zhao; Huining Deng; Peng Du; Mei Qiao; Jinlong Lu; Zengyu Wang (Desalination, 2024)

High spatiotemporal resolution ammonia emission inventory from typical industrial and agricultural province of China from 2000 to 2020 - Chuanyong Zhu; Renqiang Li; Mengyi Qiu; Changtong Zhu; Yichao Gai; Ling Li; Na Yang; Lei Sun; Chen Wang; Baolin Wang; Guihuan Yan; Chongqing Xu (Science of The Total Environment, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Unlocking hormesis and toxic effects induced by cadmium in Polygonatum cyrtonema Hua based on morphology, physiology and metabolomics - Li Yang; Yuchen Kang; Na Li; Yuhao Wang; Haiyan Mou; Hui Sun; Tianqi Ao; Li Chen; Wenqing Chen (Journal of Hazardous Materials, 2024)

Prioritization of the ecotoxicological hazard of PAHs towards aquatic species spanning three trophic levels using 2D-QSTR, read-across and machine learning-driven modelling approaches - Feifan Li; Peng Wang; Tengjiao Fan; Na Zhang; Lijiao Zhao; Rugang Zhong; Guohui Sun (Journal of Hazardous Materials, 2024)

Biopolymer films incorporated with chlorogenic acid nanoparticles for active food packaging application - Kaixuan Ma; Fan Li; Taotao Zhe; Xinyu Sun; Xinyuan Zhang; Ping Wan; Huan Na; Junnan Zhao; Li Wang (Food Chemistry, 2024)

Utilization of self-assembled soy protein nanoparticles as carriers for natural pigments: Examining non-interaction mechanisms and stability - Shi Liu; Na Sun; Kunyu Ren; Xubin Tan; Lanxin Li; Zhe Wang; Shicheng Dai; Xiaohong Tong; Huan Wang; Lianzhou Jiang (Food Hydrocolloids, 2024)

In vitro digestion and fecal fermentation of encapsulated starch constructed via layer-by-layer coating of calcium alginate - Congli Cui; Mingju Li; Xiaoyang He; Na Ji; Yang Qin; Lei Dai; Liu Xiong; Qingjie Sun (Food Hydrocolloids, 2024)

The green and low-carbon development pathways in the urban and rural building sector in Shaanxi Province, China - Tingting Zhou; Xi Luo; Xiaojun Liu; Xiongxiong Zhai; Yongkai Sun; Guangchuan Liu; Jianghua Liu; Yaru Gao; Daifeng Dang; Na Li; Pingan Feng; Yuan Gao; et al. (Energy and Buildings, 2024)

Norepinephrine-induced hydrophilic Pd aerogels with photothermal-boosted multienzyme-like activity for chemodynamic therapy of MRSA infections - Minghui Wang; Na Li; Nanyun Lin; Yingying Wu; Wei Zhou; Ximei Sun; Peixian Wu; Qian Fu; Wenjie Wang; Zheng Liu; Shuiyuan He; Mengyu Zhou; et al. (Chemical Engineering Journal, 2024)

f25, a novel synthetic quinoline derivative, inhibits tongue cancer cell invasion and survival by the PPAR pathway in vitro and vivo - Tuo Liu; Lili Yang; Zeng Li; Ming Sun; Na Lv (Chemico-Biological Interactions, 2024)

Knockdown of SIK3 in the CA1 Region can Reduce Seizure Susceptibility in Mice by Inhibiting Decreases in GABAAR α1 Expression - Zhen-Fu Jiang; Li-Na Xuan; Xiao-Wan Sun; Shao-Bo Liu; Jian Yin (Molecular Neurobiology, 2024)

Astronomical forcing and sedimentary noise modeling of lake-level changes in the Middle Eocene Chezhen Sag, Bohai Bay Basin, eastern China - Xuwei Luan; Jinliang Zhang; Na Li; Tao Chen; Long Sun; Xuecai Zhang (Frontiers of Earth Science, 2024)

Characterization of emopamil binding protein (Cs-ebp) reveals its potential role in cholesterol biosynthesis and growth performance of Chinese tongue sole - Zhangfan Chen; Xihong Li; Peng Cheng; Jiaqi Mai; Yuqi Sun; Jiacheng Wang; Rui Shi; Qi Zhang; Na Wang; Songlin Chen (Aquaculture, 2024)

The skin photoprotective effect of trilinolein: Induction of cellular autophagy via the AMPK-mTOR signaling pathway - Xianghong Lin; Na Deng; Huijuan Li; Jingxian Duan; Wenqiu Chen; Tao Liu; Sujiao Sun; Jimin Chu (Toxicology and Applied Pharmacology, 2024)

Safe utilization evaluation of two typical traditional Chinese medicinal materials in Cd-contaminated soil based on the analysis of Cd transfer and AHP model - Li Yang; Yuchen Kang; Na Li; Yuhao Wang; Hui Sun; Tianqi Ao; Li Chen; Wenqing Chen (Science of The Total Environment, 2024)

Multi-source exposure and health risks of phthalates among university students in Northeastern China - Huicheng Zhu; Na Zheng; Changcheng Chen; Ning Li; Qirui An; Wenhui Zhang; Qiuyan Lin; Zhifei Xiu; Siyu Sun; Xiaoqian Li; Yunyang Li; Sujing Wang (Science of The Total Environment, 2024)

Mechanisms and targeted reversion/prevention of hepatic fibrosis caused by the non-hereditary toxicity of benzo(a)pyrene - Xinru Du; Ming Jin; Ruzhi Li; Fei Zhou; Yuanze Sun; Qinliang Mo; Sisi Song; Na Dong; Shuoke Duan; Maoxuan Li; Ming Lu; Chi Zhang; et al. (Science of The Total Environment, 2024)

Effects of airborne pollen on allergic rhinitis and asthma across different age groups in Beijing, China - Sun Zhaobin; Zhao Yuxin; An Xingqin; Gao Na; Li Ziming; Zhang Shuwen; Liang Yinglin; Ruan Wenxi; Bu Yaqin; Xin Jingyi; Li Shihong (Science of The Total Environment, 2024)

The hysteresis damage of cold exposure on tissue and transcript levels in mice - Jing Zhang; Shiwan You; Lan Yu; Yuling Zhang; Zuoping Li; Na Zhao; Bo Zhang; Lihua Kang; Shiguo Sun (Journal of Thermal Biology, 2024)

Scutellarin targets Wnt5a against zearalenone-induced apoptosis in mouse granulosa cells in vitro and in vivo - Na Sun; Abdul Haseeb; Panpan Sun; Hua Zhang; Jia Zhong; Wei Yin; Kuohai Fan; Huizhen Yang; Zhenbiao Zhang; Yaogui Sun; Panpan Hu; Hongquan Li (Journal of Hazardous Materials, 2024)

Differentiation of antioxidants in reducing oxidation and improving quality of ready-to-eat roasted shrimp after thermal sterilization - Shuo Wang; Songyi Lin; Rui Liang; Kexin Liu; Xiuhan Chen; Lei Chen; Shuang Li; Na Sun (Food Chemistry, 2024)

Deficit irrigation and silicate spray applied since blooming period improved strawberry fruit quality without reducing fruit size - Xiangnan Xu; Xihong Lei; Guoyuan Zou; Shangqiang Liao; Na Sun; Yanxin Sun; Yanmei Li (Horticulture, Environment, and Biotechnology, 2024)

Multiple spatial scales of bacterial and fungal structural and functional traits affect carbon mineralization - Zhiyuan Ma; Shuo Jiao; Kaikai Zheng; Haowei Ni; Dong Li; Na Zhang; Yunfeng Yang; Jizhong Zhou; Bo Sun; Yuting Liang (Molecular Ecology, 2024)
Studying the functional heterogeneity of soil microorganisms at different spatial scales and linking it to soil carbon mineralization is crucial for predicting the response of soil carbon stability to environmental changes and human disturbance. Here, a total of 429 soil samples were collected from typical paddy fields in China, and the bacterial and fungal communities as well as functional genes related to carbon mineralization in the soil were analysed using MiSeq sequencing and GeoChip gene microarray technology. We postulate that CO 2 emissions resulting from bacterial and fungal carbon mineralization are contingent upon their respective carbon consumption strategies, which rely on the regulation of interactions between biodiversity and functional genes. Our results showed that the spatial turnover of the fungal community was 2–4 times that of the bacterial community from hundreds of meters to thousands of kilometres. The effect of spatial scale exerted a greater impact on the composition rather than the functional characteristics of the microbial community. Furthermore, based on the establishment of functional networks at different spatial scales, we observed that both bacteria and fungi within the top 10 taxa associated with carbon mineralization exhibited a prevalence of generalist species at the regional scale. This study emphasizes the significance of spatial scaling patterns in soil bacterial and fungal carbon degradation functions, deepening our understanding of how the relationship between microbial decomposers and soil heterogeneity impacts carbon mineralization and subsequent greenhouse gas emissions.

Optimal allocation of urban and rural water supply in coastal water shortage cities: The case of Yingkou City - Yufeng Lv; Na Yu; Haibo Sun; Hongpeng Li; Jifu Yang (Irrigation and Drainage, 2024)
Coastal cities play a significant role in regional economic development and national water resource supply. However, the shortage of water resources in coastal cities has become a bottleneck for sustainable economic, social and ecological development. As a typical coastal city in Liaoning province, China, Yingkou has a relatively developed economy, but faces increasingly serious water shortages. Taking Yingkou as a case study, this study analysed the current situation of urban and rural water supply and conducted a rational estimation of the water supply and demand based on the time series method in the short‐term (2025) and long‐term (2035). Then, the allocation of urban and rural water supply was carried out on the principle of priority use of surface water, sufficient use of diverted water, expanding use of unconventional water and limited use of underground water. To achieve the optimal scheme, the method of ‘allocation‐feedback‐regulation‐reallocation’ was adopted to coordinate the water sources and consumption in different districts and sectors. Overall, the results clarified the red line of water consumption in 2025 and 2035 and defined water consumption and water sources in different sectors and districts. Finally, the water supply and demand balance in Yingkou and its subdistricts was achieved with surplus water rates of 6% and 7% in 2025 and 2035, respectively. Based on these results, suggestions for the sustainable development and utilization of water resources in Yingkou and coastal cities were proposed.

O-acetyl-homoserine sulfhydrylase deficient Streptococcus suis serotype 2 strain SC19 becomes an avirulent strain and provides immune protection against homotype infection in mice - Tong Wu; Hexiang Jiang; Fengyang Li; Xuan Jiang; Jun Wang; Shaopeng Wei; Yi Sun; Yanyan Tian; Hong Chu; Yu Shi; Nan Zhang; Na Li; et al. (Veterinary Microbiology, 2024)

Distribution and major driving elements of antibiotic resistance genes in the soil-vegetable system under microplastic stress - Ning Li; Na Zheng; Jiamin Pan; Qirui An; Xiaoqian Li; Siyu Sun; Changcheng Chen; Huicheng Zhu; Zimeng Li; Yining Ji (Science of The Total Environment, 2024)

Co-exposure to UV-aged microplastics and cadmium induces intestinal toxicity and metabolic responses in earthworms - Changcheng Chen; Na Zheng; Huicheng Zhu; Qirui An; Jiamin Pan; Xiaoqian Li; Yining Ji; Ning Li; Siyu Sun (Journal of Hazardous Materials, 2024)

Effect of polysaccharide addition on food physical properties: A review - Zichao Wang; Lu Wang; Xiaoxue Yu; Xueqin Wang; Yi Zheng; Xilei Hu; Peiyao Zhang; Qi Sun; Qi Wang; Na Li (Food Chemistry, 2024)

Individual and combined effects of phthalate metabolites on eczema in the United States population - Xiaoqian Li; Na Zheng; Yan Yu; Wenhui Zhang; Siyu Sun; Qirui An; Zimeng Li; Yining Ji; Sujing Wang; Ying Shi; Wanlei Li (Environmental Research, 2024)

The performance and microbial community of anaerobic membrane bioreactor for high calcium papermaking wastewater treatment - Mingchao Zhu; Jingwei Wang; Danni Pei; Ji Sun; Yongze Lu; Zhaoxia Hu; Shouwen Chen; Na Li (Journal of Water Process Engineering, 2023)

Association of selenium profile with neutralizing antibody response to inactivated SARS-CoV-2 vaccination - Sikang Gao; Na Ren; Taoping Sun; Qi Nie; Sitian Liu; Xuyang Geng; Yao Deng; Zefang Lin; Yu Liu; Li Zhou (Journal of Trace Elements in Medicine and Biology, 2023)

Decarbonization potential collaborated with source industries for China's iron and steel industry towards carbon neutrality - Jingchao Sun; Ziyang Qiu; Yuxing Yuan; Zichang Che; Lei Zhang; Tao Du; Hongming Na; Yingnan Li (Journal of Cleaner Production, 2023)

Performance and reaction mechanism of Mg-doped and Li-doped La2O3 catalysts in oxidative coupling of methane: DFT and experiment study - Na Sun; Jiayu Zhang; Lixia Ling; Pengyu Niu; Riguang Zhang; Litao Jia; Debao Li; Baojun Wang (Fuel, 2023)

Tuning the oxidation level of GO to construct high performance crosslinked lamellar graphene oxide membrane for pervaporation desalination - Xiaowei Qian; Ziheng Wang; Jiawei Sun; Feixiang Zeng; Dongyun Wu; Zongli Xie; Na Li (Desalination, 2023)

Mettl13 protects against cardiac contractile dysfunction by negatively regulating C-Cbl-mediated ubiquitination of SERCA2a in ischemic heart failure - Shuting Yu; ZhiYong Sun; Xiuzhu Wang; Tiantian Ju; Changhao Wang; Yingqi Liu; Zhezhe Qu; KuiWu Liu; Zhongting Mei; Na Li; Meixi Lu; Fan Wu; et al. (Science China Life Sciences, 2023)

Temporal patterns of algae in different urban lakes and their correlations with environmental variables in Xi'an, China - Shengnan Chen; Hanyan Liu; Haihan Zhang; Kai Li; Na Wang; Weimin Sun; Xiang Liu; Limin Niu; Ben Ma; Fan Yang; Haiyun Li; Daijuan Zhao; et al. (Journal of Environmental Sciences, 2023)

Estimate of the maximum amount of dust adhering to skin and the upper limit of dust-skin adherence factor for young adults: An example from Changchun, China - Xiaoqian Li; Na Zheng; Wenhui Zhang; Siyu Sun; Qirui An; Zimeng Li; Yining Ji; Sujing Wang (Chemosphere, 2023)

Selenium improves the medicinal safety and quality of Bletilla striata by promoting the fixation of cadmium in root: Pot and field experiments - Na Li; Li Yang; Kuiwei Chen; Yuchen Kang; Yuan Cao; Hengwei Du; Haiyan Mou; Hui Sun; Tianqi Ao; Wenqing Chen (Journal of Hazardous Materials, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

Oral administration of the herbal oligonucleotide XKC-sRNA-h3 prevents angiotensin II-induced hypertension in mice - Kegong Tang; Xiaona Wang; Yu Zhao; Xiaobei Li; Zhenyu Jiang; Song Mei; Mingrui Chen; Yiming Ma; Xinyi Du; Xiangyu Qiao; Na Sun; Jiaqi Liu; et al. (Science China Life Sciences, 2023)

Microbiological Characteristics and Risk Factors Involved in Progression from Fungal Keratitis with Hypopyon to Keratitis-Related Endophthalmitis - Yu Sun; Fanxing Zeng; Jingjing Zhang; Xiaolin Qi; Xiuhai Lu; Na Ning; Suxia Li; Ting Zhang; Gongqiang Yuan; Weiyun Shi; Hua Gao (Mycopathologia, 2023)

Osteopontin targeted non-invasive nanoprobes with amplified surface plasmon resonance for photothermally enhanced multimodal precision imaging of vulnerable atherosclerotic plaques - Shaoshen Wang; Xing Zhang; Yang Liu; Ying Wang; Na Sun; Jie Yin; Jieli Bao; Gege Liao; Dongye Li; Tongda Xu; Fenglei Gao (Chemical Engineering Journal, 2023)

CS-NO suppresses inhibits glycolysis and gastric cancer progression through regulating YAP/TAZ signaling pathway - Na Guo; Hongxuan Ma; Dehui Li; Huanfang Fan; Chunxia Sun; Yunchao Sun (Cell Biochemistry and Biophysics, 2023)

Spatiotemporal dynamics, traceability analysis, and exposure risks of antibiotic resistance genes in PM2.5 in Handan, China - Qing Wang; Shengjuan Yang; Shaojing Sun; Litao Wang; Guang Yang; Jinghui Luo; Yan Sun; Xuli Li; Na Wang; Bin Chen (Environmental Science and Pollution Research, 2023)

Comprehensive analysis of lncRNA-mRNA regulatory network in Populus associated with xylem development - Na Sun; Yufen Bu; Xinyuan Wu; Xiaocen Ma; Haobo Yang; Liang Du; Xiaojuan Li; Jianwei Xiao; Jinxing Lin; Yanping Jing (Journal of Plant Physiology, 2023)

Characteristics and health risks of population exposure to phthalates via the use of face towels - Wenhui Zhang; Na Zheng; Sujing Wang; Siyu Sun; Qirui An; Xiaoqian Li; Zimeng Li; Yining Ji; Yunyang Li; Jiamin Pan (Journal of Environmental Sciences, 2023)

Phthalate exposure with sperm quality among healthy Chinese male adults: The role of sperm cellular function - Pan Yang; Lang-Jing Deng; Jin-Ying Xie; Xiao-Jie Li; Xiao-Na Wang; Bin Sun; Tian-Qing Meng; Cheng-Liang Xiong; Yi-Chao Huang; Yi-Xin Wang; An Pan; Da Chen; et al. (Environmental Pollution, 2023)

Dynamic Measurements of Cerebral Blood Flow Responses to Cortical Spreading Depolarization in the Murine Endovascular Perforation Subarachnoid Hemorrhage Model - Jin Yan; Wenlang Li; Chao Zhou; Na Wu; Xiaomin Yang; Qiuling Pan; Tao He; Yue Wu; Zongduo Guo; Yongzhi Xia; Xiaochuan Sun; Chongjie Cheng (Translational Stroke Research, 2023)

Prediction of Effector Proteins from Trichoderma longibrachiatum Through Transcriptome Sequencing - Jialin Zhang; Lijun Wang; Aizhi Ren; Yinsheng Sheng; Xue Chang; Xiaolong Li; Mengjiao Guan; Na Shang; Peibao Zhao; Shulei Sun (Current Microbiology, 2023)

Aroma correlation assisted volatilome coupled network analysis strategy to unveil main aroma-active volatiles of Rosa roxburghii - Ya-Hui Ge; Xue Li; Mingzheng Huang; Zhengxu Huang; Manman Wu; Baoqing Sun; Lishuang Wang; Jian-Lin Wu; Na Li (Food Research International, 2023)

Peroxydisulfate activation by CuFe2S3 nanocrystal doped C/N catalyst for phenanthrene degradation: Experimental, mechanism, and density functional theory calculation - Shaomeng Huang; Liping Wang; Qiongqiong He; Leilei Sun; Dan Li; Na Liu; Yaqin Zhao; Lei Yang (Chemical Engineering Journal, 2023)

Enhanced ion recognition through bi-directionally layered spacing regulation of 1D tubular titanate nanofilms - Shiyu Sun; Xin Huang; Jingtao Bi; Na Wang; Ting Wang; Lina Zhou; Li Wang; Shyam Lamichhane; Hongxun Hao (Chemical Engineering Journal, 2023)

Ecotoxicological QSAR study of fused/non-fused polycyclic aromatic hydrocarbons (FNFPAHs): Assessment and priority ranking of the acute toxicity to Pimephales promelas by QSAR and consensus modeling methods - Shuo Chen; Guohui Sun; Tengjiao Fan; Feifan Li; Yuancong Xu; Na Zhang; Lijiao Zhao; Rugang Zhong (Science of The Total Environment, 2023)

Ent-kauranes and ent-atisanes from Euphorbia wallichii and their anti-inflammatory activity - Yali Wang; Qinghua Jiang; Dejuan Sun; Na Zhang; Yu Lin; Hua Li; Lixia Chen (Phytochemistry, 2023)

A review of environmentally friendly gold lixiviants: Fundamentals, applications, and commonalities - Jinlin Li; Jue Kou; Chunbao Sun; Na Zhang; Hao Zhang (Minerals Engineering, 2023)

Ethylene carbonate generated efficiently via ethylene oxide and CO2 on the Li-MgO(1 0 0) surface based on the synergistic activation of bimetals without halogen - Yunya Guo; Jingjing Zhang; Na Sun; Lixia Ling; Riguang Zhang; Heqin Guo; Debao Li; Baojun Wang (Fuel, 2023)

Effects of sericin on oxidative stress and PI3K/AKT/mTOR signal pathway in cryopreserved mice ovarian tissue - Wei Han Shu; Song He Yang; Meng Wei; Xiao Chao Liu; Zi Xuan Chen; Chen Yang Wei; Xin Zhang; Li Na Si; Zhi Hong Chen; Yue Bing Qiao; Dong Mei Li; Tie Cheng Sun; et al. (Cryobiology, 2023)

CD33/TREM2 Signaling Mediates Sleep Deprivation-Induced Memory Impairment by Regulating Microglial Phagocytosis - Shuwen Tan; Hui Gao; Jianyu Sun; Na Li; Yuxin Zhang; Liu Yang; Min Wang; Qiang Wang; Qian Zhai (NeuroMolecular Medicine, 2023)

Temporal decline of genetic differentiation among populations of western flower thrips across an invaded range - Li-Na Sun; Li-Jun Cao; Jin-Cui Chen; Li-Jun Ma; Gui-Fen Zhang; San-An Wu; Ary Anthony Hoffmann; Shu-Jun Wei (Biological Invasions, 2023)

Study on the inactivation and reactivation mechanism of pathogenic bacteria in aquaculture by UVC-LED - Weixiao Zhang; Ruipin Huang; Tao Zhang; Baolong Wang; Na Li; Yan Sun; He Ma; Qian Zhang; Junxin Zhang; Ying Liu (Frontiers in Marine Science, 2023)
Ultraviolet disinfection is an important method for controlling the large-scale outbreaks of diseases in aquaculture. As a novel and promising light source, ultraviolet light-emitting diode (UV-LED) has the advantages of safety, high efficiency and no environmental pollution risks. However, it remains unclear whether UV-LEDs can replace traditional UV light sources for aquaculture water treatment processes. Present study aimed to investigate the efficacy of UVC-LEDs (265 nm) on pathogenic bacteria, specifically Aeromonas salmonicida and Escherichia coli . The effects of UVC-LED dose, light conditions, and temperature on bacterial reactivation were also investigated. The results showed that exposure to UVC-LED effectively inactivated both types of bacteria. To achieve 4.5-log inactivation of A. salmonicida and E. coli , 24 mJ/cm 2 and 28 mJ/cm 2 UVC-LED irradiation were required, and the inactivation rate increased with increasing UVC-LED fluence. Both A. salmonicida and E. coli were revived after UVC-LED disinfection, and photoreactivation was significantly higher than dark reactivation. Bacterial reactivation rate due to high-dose UVC-LED treatment was significantly lower than that of low-dose. After 72 h of reactivation, photoreactivation and dark reactivation rates were 1 ± 0.4% and 2.2 ± 0.2%for A. salmonicida , and 0.02% and 0% for E. coli , respectively. Besides, the photoreactivation rates for the two bacteria exhibited different correlations with temperature. The highest photoreactivation rate for A. salmonicida was 68.7 ± 4% at 20°C, while the highest photoreactivation rate for E. coli was 53.98 ± 2.9% at 15°C for 48 h. This study reveals the rapid and efficient inactivation of bacteria by UVC-LED, and elucidates the mechanism and influencing factors for inactivation and reactivation by UVC-LED. The study also highlights that adequate UVC-LED irradiation and avoidance of visible light after UVC-LED disinfection can effectively inhibit bacterial reactivation. Our findings form a reference for the design and operation of UV disinfection in aquaculture.

Impact of aqueous environments on hydrogen peroxide activation by manganese oxides: Kinetics and the critical role of bicarbonate - Na Guo; Ruochun Zhang; Jingchen Li; Zhihan Sun; Teng Fei; Peizhe Sun (Chemosphere, 2023)

Measurement and real-time monitoring of marine economic security climate in China - Xuemei Li; Shiwei Zhou; Yufeng Zhao; Na Li; Yuyu Sun (Ocean & Coastal Management, 2023)

High spatiotemporal resolution vehicular emission inventory in Beijing-Tianjin-Hebei and its surrounding areas (BTHSA) during 2000–2020, China - Chuanyong Zhu; Xinyue Qu; Mengyi Qiu; Changtong Zhu; Chen Wang; Baolin Wang; Lei Sun; Na Yang; Guihuan Yan; Chongqing Xu; Ling Li (Science of The Total Environment, 2023)

Livestock grazing-exclusion under global warming scenario decreases phosphorus mineralization by changing soil food web structure in a Tibetan alpine meadow - Feng Sun; Ruiying Chang; Akash Tariq; Jordi Sardans; Josep Penuelas; Hui Jiang; Xingmei Zhou; Na Li (Science of The Total Environment, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

In vitro antioxidant analysis of flavonoids extracted from Artemisia argyi stem and their anti-inflammatory activity in lipopolysaccharide-stimulated RAW 264.7 macrophages - Zichao Wang; Lu Wang; Hongtao Huang; Qiuyan Li; Xiaoyuan Wang; Qi Sun; Qi Wang; Na Li (Food Chemistry, 2023)

Whey protein concentrate/pullulan gel as a novel microencapsulated wall material for astaxanthin with improving stability and bioaccessibility - Yankai Liu; Xia Li; Haiyue Sun; Jing Zhang; Chunyu Cai; Na Xu; Jiale Feng; Bo Nan; Yuhua Wang; Jingsheng Liu (Food Hydrocolloids, 2023)

Graphene/carbon fiber network constructed by co-carbonization strategy for functional integrated polyimide composites with enhanced electromagnetic shielding and thermal conductive properties - Xiong Li; Tongle Xu; Wenjing Cao; Menghuan Wang; Fengqing Chen; Liyuan Jin; Na Song; Sheng Sun; Peng Ding (Chemical Engineering Journal, 2023)

Rational design of molecular phototheranostic platform for NIR-II fluorescence imaging guided chemodynamic-photothermal combined therapy - Gui-long Wu; Bin Sun; Yuxuan He; Xiaofeng Tan; Qi Pan; Sha Yang; Na Li; Minghui Wang; Peixian Wu; Fen Liu; Hao Xiao; Li Tang; et al. (Chemical Engineering Journal, 2023)

Selection of the appropriate reference genes by quantitative real-time PCR in leopard coral groupers Plectropomus leopardus - Han Zhang; Haoran Yang; Pengsuo Li; Na Zhao; Xiaojuan Chen; Yongcan Zhou; Zhenjie Cao; Yun Sun (Journal of Oceanology and Limnology, 2023)

Multiple roles of ferric chloride in preparing efficient magnetic hydrochar for sorption of methylene blue from water solutions - Xiao-Na Sun; Kun Yu; Jiong-Hua He; Yan Chen; Jian-Zhong Guo; Bing Li (Bioresource Technology, 2023)

Characteristics, chemical transformation and source apportionment of volatile organic compounds (VOCs) during wintertime at a suburban site in a provincial capital city, east China - BaoLin Wang; ZhenGuo Liu; ZiAng Li; YuChun Sun; Chen Wang; ChuanYong Zhu; Lei Sun; Na Yang; Ge Bai; GuoLan Fan; XiaoYan Sun; ZhiYong Xia; et al. (Atmospheric Environment, 2023)

Quality assessment of variable collagen tissues of sea cucumber (Stichopus japonicus) body wall under different heat treatment durations by label-Free proteomics analysis - Yi-Zhen Huang; Yi-Sha Xie; Yan-Xin Li; Mei-Yu Zhao; Na Sun; Hang Qi; Xiu-Ping Dong (Food Research International, 2023)

Discovery of novel ascorbic acid derivatives and other metabolites in fruit of Rosa roxburghii Tratt through untargeted metabolomics and feature-based molecular networking - Yaqi Zhang; Xiqing Bian; Guanyu Yan; Baoqing Sun; Wen Miao; Mingzheng Huang; Na Li; Jian-Lin Wu (Food Chemistry, 2023)

Natural edible pigments: A comprehensive review of resource, chemical classification, biosynthesis pathway, separated methods and application - Na Shen; Jiani Ren; Yanxia Liu; Wanqing Sun; Yuanrong Li; Huawei Xin; Yulei Cui (Food Chemistry, 2023)

Wet-spinning fluorescent alginate fibres achieved by doping PEI modified CPDs for multiple anti-counterfeiting - Li Song; Xiaolan Qiao; Jianxin Sun; Na Yi; Mengyue Wang; Zhihui Zhao; Ruyi Xie; Weichao Chen; Yanzhi Xia (Carbohydrate Polymers, 2023)

Influence of cadmium and copper mixtures to rhizosphere bacterial communities - Qirui An; Yunyang Li; Na Zheng; Jincai Ma; Shengnan Hou; Siyu Sun; Sujing Wang; Pengyang Li; Xiaoqian Li; Chunmei Zhao (Soil Ecology Letters, 2023)

Metagenomics analysis reveals potential pathways and drivers of piglet gut phage-mediated transfer of ARGs - Yalu Ji; Hengyu Xi; Zhen Zhao; Qiujie Jiang; Chong Chen; Xinwu Wang; Fengyang Li; Na Li; Changjiang Sun; Xin Feng; Liancheng Lei; Wenyu Han; et al. (Science of The Total Environment, 2023)

Isolation and evaluation of antioxidants from Arisaema heterophyllum tubers - Na Sun; Huanhuan Yang; Miao Zhou; Yanyan Hou; Xinru Wu; Wenqian Li; Yifang Zhang; Jinge Sun; Xin Xiong; Jihong Huang; Penghua Shu (Phytochemistry Letters, 2023)

Chemical oxidation of arsenic in the environment and its application in remediation: A mini review - Chaolei YUAN; Qi LI; Zhaoyang SUN; Wenjun ZHANG; Jiangrong CHEN; Zheng CHEN; Shuo NA; Hongwen SUN (Pedosphere, 2023)

Refractory organics removal in PMS and H2O2/PMS oxidation system activated by biochar/nZVI/MoS2 composite: Synthesis, performance, mechanism and dosing methods - Hao Sun; Baoyong Zhang; Na Wang; Nianbo Zhang; Yunqian Ma; Lihua Zang; Zhen Li; Rong Xue (Journal of Environmental Chemical Engineering, 2023)

Magnetic metal–organic frameworks as adsorbents for the detection of azo pigments in food matrices - Lei Cheng; Rong Huang; Qiang Cao; Na Liu; Peiyi Li; Mengmeng Sun; Haiyang Qin; Lidong Wu (Food Chemistry, 2023)

Liquid metal/CNTs hydrogel-based transparent strain sensor for wireless health monitoring of aquatic animals - Mengmeng Sun; Peiyi Li; Haiyang Qin; Na Liu; Hude Ma; Zhilin Zhang; Junye Li; Baoyang Lu; Xiaofang Pan; Lidong Wu (Chemical Engineering Journal, 2023)

Ecotoxicological QSAR modelling of the acute toxicity of fused and non-fused polycyclic aromatic hydrocarbons (FNFPAHs) against two aquatic organisms: Consensus modelling and comparison with ECOSAR - Feifan Li; Guohui Sun; Tengjiao Fan; Na Zhang; Lijiao Zhao; Rugang Zhong; Yongzhen Peng (Aquatic Toxicology, 2023)

An integrative analysis of lncRNAs and mRNAs highlights the potential roles of lncRNAs in the process of follicle selection in Taihang chickens - Bei-Bei Zhang; Meng-Xiao Li; Hong-Na Wang; Chao Liu; Yan-Yan Sun; Teng-He Ma (Theriogenology, 2023)

Diterpenoids with anti-inflammatory activity from Euphorbia wallichii - Yali Wang; Dejuan Sun; Qinghua Jiang; Liangliang Xiong; Na Zhang; Yingni Pan; Hua Li; Lixia Chen (Phytochemistry, 2023)

Experimental study on thermochemical composite system huff-n-puff process in ultra-heavy oil production - Na Zhang; Wei Liu; Xuefei Zou; Shaochun Wang; Qian Sun; Binfei Li; Songyan Li; Aabiskar Bhusal; Shuhua Wang; Zhaomin Li (Fuel, 2023)

Insights into enhanced oil recovery by thermochemical fluid flooding for ultra-heavy reservoirs: An experimental study - Qian Sun; Na Zhang; Wei Liu; Binfei Li; Songyan Li; Aabiskar Bhusal; Shuhua Wang; Zhaomin Li (Fuel, 2023)

Bioaccumulation of organophosphorus flame retardants in marine organisms in Liaodong Bay and their potential ecological risks based on species sensitivity distribution - Sujing Wang; Na Zheng; Siyu Sun; Yining Ji; Qirui An; Xiaoqian Li; Zimeng Li; Wenhui Zhang (Environmental Pollution, 2023)

Multimedia fates and ecological risk control strategies of phthalic acid esters in a lake recharged by reclaimed water using the QWASI fugacity model - Chenchen Wang; Jing Li; Chunsheng Qiu; Lei Wang; Xiao Su; Panpan Huang; Na He; Liping Sun; Yaohui Bai; Chaocan Li; Yufei Wang (Ecological Modelling, 2023)

Does aspirin reduce the incidence, recurrence, and mortality of hepatocellular carcinoma? A GRADE-assessed systematic review and dose–response meta-analysis - Shaodi Ma; Guangbo Qu; Chenyu Sun; Haixia Liu; Yuemeng Jiang; Ning Li; Birong Wu; Juan Gao; Linya Feng; Peng Xie; Weihang Xia; Na Hyun Kim; et al. (European Journal of Clinical Pharmacology, 2023)

Isochrysis sp. cultivation in pilot-scale to concurrently produce sustainable triacylglycerols for human milk fat substitutes and fucoxanthin - Daogui Li; Na Chen; Zhihua Zhou; Cairong Zhong; Jingping Fang; Luqiang Huang; Han Sun; Chengdeng Chi; Youcai Zhou; Yongjin He (Algal Research, 2023)

Aaptamine derivatives with CDK2 inhibitory activities from the South China Sea sponge Aaptos suberitoides - Qian-Qian He; Yu-Qing Man; Kun-Lai Sun; Li-Juan Yang; Yan Wu; Jing Du; Wei-Wei Chen; Juan-Juan Dai; Na Ni; Shuang Miao; Kai-Kai Gong (Natural Product Research, 2022)

Two new sesquiterpenoid lactone derivatives from Lindera aggregata - Song-Song Wen; Yan Wang; Jia-Ping Xu; Qi Liu; Lei Zhang; Jing Zheng; Lin Li; Na Zhang; Xin Liu; Yu-Wen Xu; Zhen-Liang Sun (Natural Product Research, 2022)

Chronological deposition record of trace metals in sediment cores from Chaohu Lake, Anhui Province, China - Xin Wang; Na Gao; Yangyang Liang; Fei Liu; Xiuping Hong; Xiujie Zhou; Liqiang Sun; Hui Li; Ting Fang (Environmental Monitoring and Assessment, 2022)

Genistein Alleviates Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus by Activating the Sirt1/Nrf2 Pathway in High Salt-Induced Hypertension - Li-Gang Niu; Na Sun; Kai-Li Liu; Qing Su; Jie Qi; Li-Yan Fu; Guo-Rui Xin; Yu-Ming Kang (Cardiovascular Toxicology, 2022)

Maternal exposure to cooking oil fumes during pregnancy and autistic‐like behaviors in Chinese preschoolers - Jian-Hui Yang; Esben Strodl; Chuan-An Wu; Xiang-Yu Hou; Xiao-Na Yin; Guo-Min Wen; Deng-Li Sun; Dan-Xia Xian; Jing-Yi Chen; Ying-Jie Chen; Jing Chen; Wei-Qing Chen (Environmental Science and Pollution Research, 2022)

Ancylostoma ceylanicum Infection in a Miniature Schnauzer Dog Breed - Xu-Hui Lin; Hai-Ming Cai; Zhuan-Qiang Yan; Shen-Quan Liao; Min-Na Lv; Cai-Yan Wu; Juan Li; Jun-Jing Hu; Wen-Wan Xiao; Jian-Fei Zhang; Nan-Shan Qi; Ming-Fei Sun (Acta Parasitologica, 2022)

Soil causes gut microbiota to flourish and total serum IgE levels to decrease in mice - Dongrui Zhou; Na Li; Fan Yang; Honglin Zhang; Zhimao Bai; Yangyang Dong; Mengjie Li; Wenyong Zhu; Zhongjie Fei; Pengfeng Xiao; Xiao Sun; Zuhong Lu (Environmental Microbiology, 2022)
Summary Traditional farm environments induce protection from allergic diseases. In this study, farm environmental factors were classified into three categories, environmental microbes, soil, and organic matter. To explore the impact of soil and environmental microorganisms on gut microbiota and immune function, mice were fed sterilized soil and inhaling microbes, soil microbes, or non‐sterilized soil. Metagenomic sequencing results showed the intake of sterile soil, that is, inhaling a small amount of soil microbes in the air increased gut microbial diversity and the abundance of type III secretion system (T3SS) genes, and decreased serum immune IgE levels induced by 2‐4‐dinitrofluorobenzene (DNFB). The intake of soil microbes increased the abundance of genes involved in the metabolism of short‐chain fatty acids and amino acid biosynthesis. Meanwhile, the intake of soil increased gut microbial diversity, the abundance of T3SS genes and related infectious elements, and genes associated with the metabolism of short‐chain fatty acids and amino acid biosynthesis, and decreased serum IgE levels. Therefore, soil may be useful as a potential ‘prebiotic’ promoting the reproduction and growth of some intestinal microorganisms that harbour bacterial secretion system genes, especially those of T3SS, whose abundance was positively and significantly correlated with innate immune function of mice.

SbWRKY55 regulates sorghum response to saline environment by its dual role in abscisic acid signaling - Yushuang Song; Hongxiang Zheng; Yi Sui; Simin Li; Fenghui Wu; Xi Sun; Na Sui (Theoretical and Applied Genetics, 2022)

Identification of SEC14 like lipid binding 2(SEC14L2) sequence and expression profiles in the Chinese tree shrew (Tupaia belangeri chinensis) - Dandan Qiu; Xiuying Kui; Wenguang Wang; Na Li; Pinfen Tong; Xiaomei Sun; Caixia Lu; Jiejie Dai (Molecular Biology Reports, 2022)

Review on visualization technology in simulation training system for major natural disasters - Ning Li; Na Sun; Chunxia Cao; Shike Hou; Yanhua Gong (Natural Hazards, 2022)

Association between MAP3K4 gene polymorphisms and the risk of schizophrenia susceptibility in a Northeast Chinese Han population - Yang Sun; Ye Lv; Hui-Wen Ren; Guan-Yu Wang; Li-Na Xuan; Yi-Yang Luo; Zhi-Lin Luan (Metabolic Brain Disease, 2022)

Study of the heterologous gene expression characteristics of a new clone of a cell line derived from Papilio xuthus and its serum-free adaptation - Wei-Feng Ding; Na Sun; Zhi-Gang Liu; Xin Zhang; Xian Li; Hang Chen; Ying Feng (In Vitro Cellular & Developmental Biology - Animal, 2022)

Alkaloids constituents from the roots of Phragmites australis (Cav.) Trin. ex Steud. with their cytotoxic activities - Ying Chen; Li Li; Li-Rui Jiang; Jia-Yin Tan; Li-Na Guo; Xiao-Li Wang; Wei Dong; Wen-Bao Wang; Ji-Kai Sun; Bo Song (Natural Product Research, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Mass cultivation of conidia of Pyricularia oryzae - Zhong-na Hao; Hai-ping Qiu; Zhen Zhang; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2022)

MiR-582-3p participates in the regulation of biological behaviors of A549 cells by ambient PM2.5 exposure - Mei Yang; Liangliang Ju; Changlian Li; Han Cheng; Na Li; Qi Zhang; Shu Sun; Liu Ding; Xinmiao Sui; Chao Zhang; Mingwei Yang; Jiyu Cao; et al. (Environmental Science and Pollution Research, 2022)

Trends and Health Risk of Trace Metals in Fishes in Liaodong Bay, China, From 2015 to 2020 - Sujing Wang; Na Zheng; Siyu Sun; Qirui An; Pengyang Li; Xiaoqian Li; Zimeng Li; Wenhui Zhang (Frontiers in Marine Science, 2022)
Due to their toxicity, non-biodegradability, and biological amplification in the food chain, heavy metal accumulation in humans via the consumption of fishes has become a problem. In this study, we analyzed the concentrations of six trace metals (Cd, Cr, Cu, Ni, Pb, Zn) in 12 marine fish species collected from Liaodong Bay, China, from 2015 to 2020, to understand the pollution status of the bay and evaluate the impact of fish consumption on human health. In addition, 5 fish species with the potential to serve as bioindicators of metal contamination were identified. In general, the average concentrations were Zn > Pb ≈ Cr > Ni ≈ Cu > Cd. There were significant differences in the concentrations in the muscle tissues of fish with different feeding strategies. The total target hazard quotient values of some fish were greater than 1 in 2015, suggesting that people were susceptible to high health risks. The year 2017 had the lowest values, which suggests that metal pollution in Liaodong Bay may have been decreasing at that time. Monitoring of metal concentrations in marine fish from Liaodong Bay warrants more study.

SbbHLH85, a bHLH member, modulates resilience to salt stress by regulating root hair growth in sorghum - Yushuang Song; Simin Li; Yi Sui; Hongxiang Zheng; Guoliang Han; Xi Sun; Wenjing Yang; Hailian Wang; Kunyang Zhuang; Fanying Kong; Qingwei Meng; Na Sui (Theoretical and Applied Genetics, 2022)

Characterization and Cys-directed mutagenesis of urate oxidase from Bacillus subtilis BS04 - Tong-tong Zhu; Hong-na Chen; Lei Yang; Ying-bao Liu; Wei Li; Wen-xiu Sun (Biologia, 2022)

Molecular cloning and characterization of NPC1L1 in the Chinese tree shrew (Tupaia belangeri chinensis) - Xiuying Kui; Dandan Qiu; Wenguang Wang; Na Li; Pinfen Tong; Xiaomei Sun; Liangzi Jin; Wei Deng; Jiejie Dai; Caixia Lu (Molecular Biology Reports, 2021)

Differences in pathogenicity and physiologic races between Pyricularia oryzae isolates from indica and japonica rice varieties - Zhong-na Hao; Zhen Zhang; Hai-ping Qiu; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2021)

Spatial and temporal characteristics of harmful algal blooms in Zhejiang Province waters during 1933–2018 - Wen Shiyong; Sun Tianli; Wang Zizhu; Li Fei; Li Dongmei; Liu Na (Marine Biology Research, 2021)

Proteome landscape and spatial map of mouse primordial germ cells - Pan Wang; Yilong Miao; Xiao-Han Li; Na Zhang; Qilong Wang; Wei Yue; Shao-Chen Sun; Bo Xiong; Jie Qiao; Mo Li (Science China Life Sciences, 2021)

Pseudomonas laoshanensis sp. nov., isolated from peanut field soil - Ming-Qing Wang; Chu-Shu Zhang; Li-Na Yu; Wei-Qiang Yang; Kun Jiao; Kui-Jie Gong; Xiao-Yuan Chi; Jie Bi; Yu Song; Qing-Li Yang; Jian-Cheng Zhang; Gui-Wen Yang; et al. (Archives of Microbiology, 2021)

Divalent tranylcypromine derivative as lysine-specific demethylase 1 inhibitor - Yin Sun; Na Li; Mingbo Su; Xiaowen Wang; Dongmei Zhao; Bing Xiong; Yubo Zhou; Tongchao Liu; Yue-Lei Chen (Medicinal Chemistry Research, 2021)

Improving the observation and prediction capabilities for Arctic marine environment: from the perspective of Arctic Shipping - Hui Wang; Qizhen Sun; Lin Zhang; Xi Liang; Qinghua Yang; Na Liu; Chunhua Li; Qingsheng Liu; Bingrui Li; Qian Feng; Xiao Cheng; Yi Yu (Acta Oceanologica Sinica, 2021)

Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

Correction to: Shuangxia decoction alleviates p-chlorophenylalanine induced insomnia through the modification of serotonergic and immune system - Yujie Sun; Wenhui Pei; Na Zhang; Yuxia Qu; Yijia Cao; Jianhao Li; Yuwei Yang; Tiange Yang; Fang Fang; Yikun Sun (Metabolic Brain Disease, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

Activation of p62-Keap1-Nrf2 Pathway Protects 6-Hydroxydopamine-Induced Ferroptosis in Dopaminergic Cells - Yiran Sun; Libo He; Taoyu Wang; Wan Hua; Huan Qin; Jingjin Wang; Li Wang; Wanqin Gu; Tingting Li; Na Li; Xinanbei Liu; Fang Chen; et al. (Molecular Neurobiology, 2020)

Profile and development of microsatellite primers for Acanthogobius ommaturus based on high-throughput sequencing technology - Chenyu Song; Ziyi Feng; Chunhou Li; Zhicheng Sun; Tianxiang Gao; Na Song; Lu Liu (Journal of Oceanology and Limnology, 2020)

Screening for natural inhibitors of human topoisomerases from medicinal plants with bio-affinity ultrafiltration and LC–MS - Minxia Fan; Guilin Chen; Baoqing Sun; Jianlin Wu; Na Li; Satyajit D. Sarker; Lutfun Nahar; Mingquan Guo (Phytochemistry Reviews, 2020)

A fundamental theorem for eco-environmental surface modelling and its applications - Tianxiang Yue; Na Zhao; Yu Liu; Yifu Wang; Bin Zhang; Zhengping Du; Zemeng Fan; Wenjiao Shi; Chuanfa Chen; Mingwei Zhao; Dunjiang Song; Shihai Wang; et al. (Science China Earth Sciences, 2020)

Benzophenone glycosides from the pericarps of Aquilaria yunnanensis S. C. Huang - Hui Sun; Yun-Feng Zhang; Hui-Xia Huo; Peng-Wei Guan; Chao-Chao Wang; Hui-Na Yao; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2020)

Isolation and identification of two new strains of mammalian orthoreovirus from Chinese tree shrews - Xiaofei Li; Xiaomei Sun; Caixia Lu; Dexuan Kuang; Yuanyuan Han; Wenguang Wang; Pinfen Tong; Na Li; Jingxian Zhou; Jiejie Dai (Archives of Virology, 2020)

Screening of single-cell clonal lines from Papilio demoleus Linnaeus cell lines for exogenous protein expression and adaptation in serum-free culture - Wei-Feng Ding; Zhi-Gang Liu; Na Sun; Xin Zhang; Xian Li; Ying Feng (In Vitro Cellular & Developmental Biology - Animal, 2020)

Genome-Wide Identification, Phylogeny, and Expressional Profiles of the Mitogen-Activated Protein Kinase Kinase Kinase (MAPKKK) Gene Family in Pyropia yezoensis - Fanna Kong; Min Cao; Na Li; Bin Sun; Meijuan Sun; Yunxiang Mao (Frontiers in Marine Science, 2020)

Identification and validation of the superior alleles for wheat kernel traits detected by genome-wide association study under different nitrogen environments - Na Zhang; Xilan Zhang; Liqiang Song; Qiannan Su; Shuai Zhang; Jiajia Liu; Wei Zhang; Xiaoyi Fu; Minghui Zhao; Lijing Sun; Jun Ji; Wenchen Qiao; et al. (Euphytica, 2020)

Characteristics and temporal variations of organic and elemental carbon aerosols in PM1 in Changchun, Northeast China - Na Li; Xin Wei; Weizheng Han; Siyue Sun; Jinghui Wu (Environmental Science and Pollution Research, 2020)

Co-expression Network of mRNAs and lncRNAs Regulated by Stress-Linked Behavioral Assays - Jianghong Zhang; Meiying Xue; Yue Mei; Zhigang Li; Zeng Ceng; Yuanyuan Li; Yi Zhang; Na Li; Huajing Teng; Zhong Sheng Sun; Yan Wang (Psychopharmacology, 2020)

Shuangxia decoction alleviates p-chlorophenylalanine induced insomnia through the modification of serotonergic and immune system - Yujie Sun; Na Zhang; Yuxia Qu; Yijia Cao; Jianhao Li; Yuwei Yang; Tiange Yang; Yikun Sun (Metabolic Brain Disease, 2020)

Chemical constituents from Ginkgo biloba leaves and their cytotoxicity activity - Penghua Shu; Mengyuan Sun; Junping Li; Lingxiang Zhang; Haichang Xu; Yueyue Lou; Zhiyu Ju; Xialan Wei; Wenming Wu; Na Sun (Journal of Natural Medicines, 2020)

Hirsutella sinensis inhibits NLRP3 inflammasome activation to block aristolochic acid-induced renal tubular epithelial cell transdifferentiation - Min Yu; Yu-lin Man; Meng-hua Chen; Li-hua Wu; Yi Zhou; Xiao-ling Zhou; Na Chen; Rui Ma; Li-na Sun (Human Cell, 2020)

Multiple attenuation using λ-f domain high-order and high-resolution Radon transform based on SL0 norm - Wen-Zhi Sun; Zhen-Chun Li; Ying-Ming Qu; Zhi-Na Li (Applied Geophysics, 2019)

A female attractant for the blue gum chalcid, Leptocybe invasa (Hymenoptera: Eulophidae), from host plant (DH 201-2: Eucalyptus grandis × Eucalyptus tereticornis) - Tao Ma; Laijiao Lan; Na Lin; Lifei Zheng; Zhaohui Sun; Yizhen Li; Xiujun Wen (Arthropod-Plant Interactions, 2019)

Nitrogen and phosphorus removal comparison between periphyton on artificial substrates and plant-periphyton complex in floating treatment wetlands - Xueping Gao; Yan Wang; Bowen Sun; Na Li (Environmental Science and Pollution Research, 2019)

Pseudomonas qingdaonensis sp. nov., an aflatoxin-degrading bacterium, isolated from peanut rhizospheric soil - Ming-Qing Wang; Zhen Wang; Li-Na Yu; Chu-Shu Zhang; Jie Bi; Jie Sun (Archives of Microbiology, 2019)

Seminal Plasma Exosomes: Promising Biomarkers for Identification of Male and Pseudo-Males in Cynoglossus semilaevis - Bo Zhang; Na Zhao; Lei Jia; Kang Peng; Jinyuan Che; Kunming Li; Xiaoxu He; Jinsheng Sun; Baolong Bao (Marine Biotechnology, 2019)

Membrane biofouling retardation by zwitterionic peptide and its impact on the bacterial adhesion - Si-Yu Wang; Deng-Cheng Han; Chao Song; Meng-Na Li; Muhammad Zaheer Afzal; Shu-Guang Wang; Xue-Fei Sun (Environmental Science and Pollution Research, 2019)

Two new polyketides from the fungus Penicillium oxalicum MHZ153 - Yi Ren; Ling-Hui Chao; Jing Sun; Xiao-Nan Chen; Hui-Na Yao; Zhi-Xiang Zhu; Dan Dong; Ting Liu; Peng-Fei Tu; Jun Li (Natural Product Research, 2019)

Upper and Lower Bound Interval Forecasting Methodology Based on Ideal Boundary and Multiple Linear Regression Models - Wei Li; Jianzhong Zhou; Lu Chen; Kuaile Feng; Hairong Zhang; Changqing Meng; Na Sun (Water Resources Management, 2019)

Genomic Selection Using BayesCπ and GBLUP for Resistance Against Edwardsiella tarda in Japanese Flounder (Paralichthys olivaceus) - Yang Liu; Sheng Lu; Feng Liu; Changwei Shao; Qian Zhou; Na Wang; Yangzhen Li; Yingming Yang; Yingping Zhang; Hejun Sun; Weiwei Zheng; Songlin Chen (Marine Biotechnology, 2018)

Heterocapsa bohaiensis sp. nov. (Peridiniales: Dinophyceae): a novel marine dinoflagellate from the Liaodong Bay of Bohai Sea, China - Jie Xiao; Na Sun; Yiwen Zhang; Ping Sun; Yan Li; Min Pang; Ruixiang Li (Acta Oceanologica Sinica, 2018)

Cloning and characterization of SucNHX1, a novel vacular Na+/H+ antiporter from the halophyte Suaeda corniculata that enhances the saline-alkali tolerance in Arabidopsis by its overexpression - Xiaowei Li; Fawei Wang; Daqian Sun; Nan Wang; Yuanyuan Dong; Weican Liu; Xiuming Liu; Na Yao; Huan Chen; Menghan Chi; Shuhan Ji; Shijin Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Alterations of ATP-sensitive K+ channels in human umbilical arterial smooth muscle during gestational diabetes mellitus - Hongliang Li; Sung Eun Shin; Mi Seon Seo; Jin Ryeol An; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Jeeyoung Kim; Mi-Jin Yim; Jeong Min Lee; Tae Gyu An; Jihan Jeon; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

HNMDA: heterogeneous network-based miRNA–disease association prediction - Li-Hong Peng; Chuan-Neng Sun; Na-Na Guan; Jian-Qiang Li; Xing Chen (Molecular Genetics and Genomics, 2018)

Genome-wide identification and expression pattern analysis under abiotic stress of mitogen-activated protein kinase genes in Pyropia yezoensis - Chao Li; Fanna Kong; Peipei Sun; Guiqi Bi; Na Li; Yunxiang Mao; Meijuan Sun (Journal of Applied Phycology, 2018)

Simultaneous accelerated solvent extraction and purification for the determination of 13 organophosphate esters in soils by gas chromatography-tandem mass spectrometry - Qing Luo; Shiyu Wang; Li-na Sun; Hui Wang (Environmental Science and Pollution Research, 2018)

Inhibition of the Voltage-Dependent K+ Current by the Tricyclic Antidepressant Desipramine in Rabbit Coronary Arterial Smooth Muscle Cells - Sung Eun Shin; Hongliang Li; Jin Ryeol An; Mi Seon Seo; Sung Hun Na; Won-Kyo Jung; Amy L. Firth; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Il-Whan Choi; Won Sun Park (Cardiovascular Toxicology, 2018)

Immunization with an adenovirus-vectored TB vaccine containing Ag85A-Mtb32 effectively alleviates allergic asthma - Yiling Zhang; Ying Feng; Liang Li; Xianmiao Ye; Jinlin Wang; Qian Wang; Pingchao Li; Na Li; Xuehua Zheng; Xiang Gao; Chufang Li; Feng Li; et al. (Journal of Molecular Medicine, 2018)

Alternative oxidase functions in the excess excitation energy-induced resistance to pathogen infection - Qin-zheng Hou; Kun Sun; Ling-yun Jia; Jun-yu Liang; Jia-jia Xie; Li-na Lu; Han-qing Feng; Jing Wen (Biologia, 2018)

Available forms of nutrients and heavy metals control the distribution of microbial phospholipid fatty acids in sediments of the Three Gorges Reservoir, China - Hongyang Sun; Yanhong Wu; Haijian Bing; Jun Zhou; Na Li (Environmental Science and Pollution Research, 2018)

A single nucleotide mutation of IspF gene involved in the MEP pathway for isoprenoid biosynthesis causes yellow-green leaf phenotype in rice - Rui Huang; Yang Wang; Pingrong Wang; Chunmei Li; Fuliang Xiao; Nenggang Chen; Na Li; Caixia Li; Changhui Sun; Lihua Li; Rongjun Chen; Zhengjun Xu; et al. (Plant Molecular Biology, 2018)

A Highly Selective Naphthalimide-Based Chemosensor: “Naked-Eye” Colorimetric and Fluorescent Turn-On Recognition of Al3+ and Its Application in Practical Samples, Test Paper and Logic Gate - Na-Na Li; Shuang Zeng; Ming-Qiang Li; Yu-Qing Ma; Xue-Jiao Sun; Zhi-Yong Xing; Jin-Long Li (Journal of Fluorescence, 2018)

The complete mitochondrial genome of Damora sagana and phylogenetic analyses of the family Nymphalidae - Naiyi Liu; Na Li; Pengyu Yang; Chunqin Sun; Jie Fang; Shuyan Wang (Genes & Genomics, 2018)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Overexpression of PLK3 Mediates the Degradation of Abnormal Prion Proteins Dependent on Chaperone-Mediated Autophagy - Hui Wang; Chan Tian; Jing Sun; Li-Na Chen; Yan Lv; Xiao-Dong Yang; Kang Xiao; Jing Wang; Cao Chen; Qi Shi; Qi-Xiang Shao; Xiao-Ping Dong (Molecular Neurobiology, 2017)

Developing the science product algorithm testbed for Chinese next-generation geostationary meteorological satellites: Fengyun-4 series - Min Min; Chunqiang Wu; Chuan Li; Hui Liu; Na Xu; Xiao Wu; Lin Chen; Fu Wang; Fenglin Sun; Danyu Qin; Xi Wang; Bo Li; et al. (Journal of Meteorological Research, 2017)

Genome-wide identification of SAUR genes in watermelon (Citrullus lanatus) - Na Zhang; Xing Huang; Yaning Bao; Bo Wang; Hongxia Zeng; Weishun Cheng; Mi Tang; Yuhua Li; Jian Ren; Yuhong Sun (Physiology and Molecular Biology of Plants, 2017)

A novel Enterovirus 96 circulating in China causes hand, foot, and mouth disease - Yi Xu; Yisuo Sun; Jinmin Ma; Shuru Zhou; Wei Fang; Jiawei Ye; Limei Tan; Jingkai Ji; Dan Luo; Liqiang Li; Jiandong Li; Chunxiao Fang; et al. (Virus Genes, 2017)

A Novel Wheat Nicotianamine Synthase Gene, TaNAS-D, Confers High Salt Tolerance in Transgenic Arabidopsis - Jie Han; Wei Zhang; Lijing Sun; Qiannan Su; Zijing Li; Xiaoli Fan; Na Zhang; Ruiqing Pan; Fa Cui; Jun Ji; Hui Li; Junming Li (Plant Molecular Biology Reporter, 2017)

The Brain NO Levels and NOS Activities Ascended in the Early and Middle Stages and Descended in the Terminal Stage in Scrapie-Infected Animal Models - Li-Na Chen; Jing Sun; Xiao-Dong Yang; Kang Xiao; Yan Lv; Bao-Yun Zhang; Wei Zhou; Cao Chen; Chen Gao; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2017)

Activation of group I metabotropic glutamate receptors regulates the excitability of rat retinal ganglion cells by suppressing Kir and I h - Qian Li; Peng Cui; Yanying Miao; Feng Gao; Xue-Yan Li; Wen-Jing Qian; Shu-Xia Jiang; Na Wu; Xing-Huai Sun; Zhongfeng Wang (Brain Structure and Function, 2017)

Identification and functional analysis of the GTPV bidirectional promoter region - Hui Zhang; Zhihua Sun; Na Zhang; Zhiqiang Li; Pengyan Wang; Qiang Fu; Yan Ren; Xuehua Shao; Yu Zhang; Zhiru Guo; Chuangfu Chen (Archives of Microbiology, 2017)

Treatment of SMB-S15 Cells with Resveratrol Efficiently Removes the PrPSc Accumulation In Vitro and Prion Infectivity In Vivo - Jing Wang; Bao-Yun Zhang; Jin Zhang; Kang Xiao; Li-Na Chen; Hui Wang; Jing Sun; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2016)

Proteomic Analyses for the Global S-Nitrosylated Proteins in the Brain Tissues of Different Human Prion Diseases - Li-Na Chen; Qi Shi; Bao-Yun Zhang; Xiao-Mei Zhang; Jing Wang; Kang Xiao; Yan Lv; Jing Sun; Xiao-Dong Yang; Cao Chen; Wei Zhou; Jun Han; et al. (Molecular Neurobiology, 2016)

Research progress of the role and mechanism of extracellular signal-regulated protein kinase 5 (ERK5) pathway in pathological pain - Li-na Yu; Li-hong Sun; Min Wang; Min Yan (Journal of Zhejiang University-SCIENCE B, 2016)

First report of human salivirus/klassevirus in respiratory specimens of a child with fatal adenovirus infection - Na Pei; Jiaosheng Zhang; Jinmin Ma; Liqiang Li; Meng Li; Jiandong Li; Yisuo Sun; Jingkai Ji; Hui Jiang; Yong Hou; Fengping Xu; Haorong Lu; et al. (Virus Genes, 2016)

Complement receptor activity of recombinant porcine CR1-like protein expressed in a eukaryotic system - Wei Yin; Xiaoming Wei; Junbing Jiang; Kuohai Fan; Junxing Zhao; Na Sun; Zhiwei Wang; Yaogui Sun; Haili Ma; Xin Zhao; Hongquan Li (Immunologic Research, 2016)

Loci and candidate gene identification for resistance to Phytophthora sojae via association analysis in soybean [Glycine max (L.) Merr.] - Lihong Li; Na Guo; Jingping Niu; Zili Wang; Xiaoxia Cui; Jutao Sun; Tuanjie Zhao; Han Xing (Molecular Genetics and Genomics, 2016)

Metabolomic analysis of competent larvae and juvenile veined rapa whelks (Rapana venosa) - Hao Song; Li-Yuan Sun; Zheng-Lin Yu; Li-Na Sun; Dong-Xiu Xue; Tao Zhang; Hai-Yan Wang (Marine Biology, 2016)

A wind tunnel study of sand-cemented bodies on wind erosion intensity and sand transport - Jie Zhou; Jiaqiang Lei; Shengyu Li; Haifeng Wang; Na Sun; Xuexi Ma (Natural Hazards, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Remarkable Activation of the Complement System and Aberrant Neuronal Localization of the Membrane Attack Complex in the Brain Tissues of Scrapie-Infected Rodents - Yan Lv; Cao Chen; Bao-Yun Zhang; Kang Xiao; Jing Wang; Li-Na Chen; Jing Sun; Chen Gao; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2015)

Knockdown of PFTK1 Inhibits the Migration of Glioma Cells - Shaochen Fan; Chengjin Zhao; Li Zhang; Shirong Dai; Jianbing Ren; Xiubing Zhang; Na Ban; Xiaojuan He; Lixiang Yang; Zhen Bao; Wenjuan Chen; Jie Sun; et al. (Journal of Molecular Neuroscience, 2015)

Identification of insecticidal constituents of the essential oils of Dahlia pinnata Cav. against Sitophilus zeamais and Sitophilus oryzae - Da-Cheng Wang; Da-Ren Qiu; Li-Na Shi; Hong-Yu Pan; Ya-Wei Li; Jin-Zhu Sun; Ying-Jie Xue; Dong-Sheng Wei; Xiang Li; Ya-Mei Zhang; Jian-Chun Qin (Natural Product Research, 2015)

LYG-202 exerts antitumor effect on PI3K/Akt signaling pathway in human breast cancer cells - Yue Zhao; Xiaoping Wang; Yang Sun; Yuxin Zhou; Yuehan Yin; Youxiang Ding; Zhiyu Li; Qinglong Guo; Na Lu (Apoptosis, 2015)

Notch3/Akt signaling contributes to OSM-induced protection against cardiac ischemia/reperfusion injury - Mingming Zhang; Chen Wang; Jianqiang Hu; Jie Lin; Zhijing Zhao; Min Shen; Haokao Gao; Na Li; Min Liu; Pengfei Zheng; Cuiting Qiu; Erhe Gao; et al. (Apoptosis, 2015)

Potential probiotic attributes of a new strain of Bacillus coagulans CGMCC 9951 isolated from healthy piglet feces - Shao-Bin Gu; Li-Na Zhao; Ying Wu; Shi-Chang Li; Jian-Rui Sun; Jing-Fang Huang; Dan-Dan Li (World Journal of Microbiology and Biotechnology, 2015)

Establishment and characterization of a gonad cell line from half-smooth tongue sole Cynoglossus semilaevis pseudomale - Ai Sun; Song-Lin Chen; Feng-Tao Gao; Hai-Long Li; Xiao-Feng Liu; Na Wang; Zhen-Xia Sha (Fish Physiology and Biochemistry, 2015)

Scrapie Infection in Experimental Rodents and SMB-S15 Cells Decreased the Brain Endogenous Levels and Activities of Sirt1 - Jing Wang; Jin Zhang; Qi Shi; Bao-Yun Zhang; Cao Chen; Li-Na Chen; Jing Sun; Hui Wang; Kang Xiao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2015)

Transcriptome sequencing and analysis of sweet osmanthus (Osmanthus fragrans Lour.) - Hong Na Mu; Huo Gen Li; Liang Gui Wang; Xiu Lian Yang; Tao Ze Sun; Chen Xu (Genes & Genomics, 2014)

Geochemical characteristics and their significances of rare-earth elements in deep-water well core at the Lingnan Low Uplift Area of the Qiongdongnan Basin - Zhipeng Sun; Shikui Zhai; Chun Xiu; Xinyu Liu; Tong Zong; Wei Luo; Xiaofeng Liu; Kui Chen; Na Li (Acta Oceanologica Sinica, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Genetic characterization of an isolate of canine distemper virus from a Tibetan Mastiff in China - Weike Li; Tiansong Li; Yuxiu Liu; Yuwei Gao; Songtao Yang; Na Feng; Heting Sun; Shengle Wang; Lei Wang; Zhigao Bu; Xianzhu Xia (Virus Genes, 2014)

Association mapping for partial resistance to Phytophthora sojae in soybean (Glycine max (L.) Merr.) - JUTAO SUN; NA GUO; JUN LEI; LIHONG LI; GUANJUN HU; HAN XING (Journal of Genetics, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

p-Synephrine suppresses lipopolysaccharide-induced acute lung injury by inhibition of the NF-κB signaling pathway - Qianchao Wu; Ruisheng Li; Lanan Wassy Soromou; Na Chen; Xue Yuan; Guoquan Sun; Beibei Li; Haihua Feng (Inflammation Research, 2014)

Genetic analysis and fine mapping of RpsJS, a novel resistance gene to Phytophthora sojae in soybean [Glycine max (L.) Merr.] - Jutao Sun; Lihong Li; Jinming Zhao; Jing Huang; Qiang Yan; Han Xing; Na Guo (Theoretical and Applied Genetics, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Synthesis and analgesic evaluation of a series of proline-typed spiro cyclic quaternary ammoniums - Songwen Lin; Na Wang; Shuo Zhao; Qi Sun; Weiwei Zhang; Jia Ye; Tieming Cheng; Runtao Li (Medicinal Chemistry Research, 2014)

Dishevelled-1 (Dvl-1) Protein: a Potential Participant of Oxidative Stress Induced by Selenium Deficiency - Han-dong Zhao; Mei-na Sun; Meng-di Li; Feng-lan Li; Hui Li (Biological Trace Element Research, 2014)

Structure and dynamics of the bacterial communities in fermentation of the traditional Chinese post-fermented pu-erh tea revealed by 16S rRNA gene clone library - Ming Zhao; Wei Xiao; Yan Ma; Tingting Sun; Wenxia Yuan; Na Tang; Donglian Zhang; Yongxia Wang; Yali Li; Hongjie Zhou; Xiaolong Cui (World Journal of Microbiology and Biotechnology, 2013)

The ecological implications of land use change in the Source Regions of the Yangtze and Yellow Rivers, China - Li Na; Wang Genxu; Liu Guangsheng; Lin Yun; Sun Xiangyang (Regional Environmental Change, 2013)

The detection of QTLs controlling bacterial wilt resistance in tobacco (N. tabacum L.) - Yi-liang Qian; Xin-sheng Wang; Da-zhou Wang; Li-na Zhang; Chao-long Zu; Zheng-liang Gao; Hong-jun Zhang; Zhi-yong Wang; Xue-yong Sun; Da-nian Yao (Euphytica, 2013)

Iodine Excess Induces Hepatic Steatosis Through Disturbance of Thyroid Hormone Metabolism Involving Oxidative Stress in BaLB/c Mice - Yun Xia; Wei Qu; Li-Na Zhao; Hao Han; Xue-Feng Yang; Xiu-Fa Sun; Li-Ping Hao; Jian Xu (Biological Trace Element Research, 2013)

Regurgitant Derived From the Tea Geometrid Ectropis obliqua Suppresses Wound-Induced Polyphenol Oxidases Activity in Tea Plants - Zi-Wei Yang; Xiao-Na Duan; Shan Jin; Xi-Wang Li; Zong-Mao Chen; Bing-Zhong Ren; Xiao-Ling Sun (Journal of Chemical Ecology, 2013)

Partial or complete substitution of fish meal with soybean meal and cottonseed meal in Chinese mitten crab Eriocheir sinensis diets - Hai-Bo Jiang; Li-Qiao Chen; Jian-Guang Qin; Lu-Jiao Gao; Er-Chao Li; Na Yu; Sheng-Ming Sun; Xue-Qin Jiang (Aquaculture International, 2013)

Tetrodotoxin attenuates isoproterenol-induced hypertrophy in H9c2 rat cardiac myocytes - Ming-Zi Chen; Qing-Ting Bu; Shu-Chao Pang; Feng-Lan Li; Mei-Na Sun; Er-Fu Chu; Hui Li (Molecular and Cellular Biochemistry, 2012)

Benfotiamine prevents increased β-amyloid production in HEK cells induced by high glucose - Xiao-Jing Sun; Lei Zhao; Na Zhao; Xiao-Li Pan; Guo-Qiang Fei; Li-Rong Jin; Chun-Jiu Zhong (Neuroscience Bulletin, 2012)

Involvement of FGF9/16/20 subfamily in female germ cell development of the Nile tilapia, Oreochromis niloticus - Yun-Lv Sun; Sheng Zeng; Kai Ye; Chao Yang; Ming-Hui Li; Bao-Feng Huang; Li-Na Sun; Lin-Yan Zhou; De-Shou Wang (Fish Physiology and Biochemistry, 2012)

Polymorphisms in luteinizing hormone receptor and hypothalamic gonadotropin-releasing hormone genes and their effects on sperm quality traits in Chinese Holstein bulls - Li-Ping Sun; Qing-Zhi Du; Ya-Pan Song; Jun-Na Yu; Shu-Juan Wang; Lei Sang; Luo-Wen Song; Yao-Min Yue; Yu-Ze Lian; Sheng-Li Zhang; Guo-Hua Hua; Shu-Jun Zhang; et al. (Molecular Biology Reports, 2012)

Perfluoroalkyl compounds in municipal WWTPs in Tianjin, China—concentrations, distribution and mass flow - Hongwen Sun; Xianzhong Zhang; Lei Wang; Tao Zhang; Fasong Li; Na He; Alfredo C. Alder (Environmental Science and Pollution Research, 2012)

Purification, Characterization, and Expression Analysis of a Putative Lectin in Peanut (Arachis hypogaea L.) - Sun Jie; Zhang Chu-shu; Yu Li-na; Bi Jie; Liu Shao-fang; Zhu Feng; Yang Qing-li (Plant Molecular Biology Reporter, 2012)

Organ Histopathological Changes and its Function Damage in Mice Following Long-term Exposure to Lanthanides Chloride - Jie Cheng; Na Li; Jingwei Cai; Zhe Cheng; Renping Hu; Qian Zhang; Fangfang Wan; Qingqing Sun; Suxing Gui; Xuezi Sang; Ling Wang; Fashui Hong (Biological Trace Element Research, 2012)

Determination of aflatoxins in edible oil from markets in Hebei Province of China by liquid chromatography–tandem mass spectrometry - Li-xin Yang; Yin-ping Liu; Hong Miao; Bin Dong; Na-jing Yang; Feng-qi Chang; Li-xue Yang; Jing-bo Sun (Food Additives & Contaminants Part B-Surveillance, 2011)

Effect of Different Iodine Nutrition on Cerebellum Pcp-2 in Rat Offspring During Lactation - Lu Zhang; Yi Na Sun; Yong Mei Li; Lai Xiang Lin; Yan Ye; Yu Qin Yan; Zu Pei Chen (Biological Trace Element Research, 2011)

Suboptimal Selenium Supply—A Continuing Problem in Keshan Disease Areas in Heilongjiang Province - Jie Hou; Tong Wang; Mingfa Liu; Shaochen Li; Jie Chen; Chunxu Liu; Hui Zhang; Yiru Wang; Zengchao Liu; Na Liang; Yuezhu Wan; Qi Li; et al. (Biological Trace Element Research, 2011)

Supplemental Selenium Alleviates the Toxic Effects of Excessive Iodine on Thyroid - Jian Xu; Xiao-Li Liu; Xue-Feng Yang; Huai-Lan Guo; Li-na Zhao; Xiu-Fa Sun (Biological Trace Element Research, 2011)

Trace analysis of persistent toxic substances in the main stream of Jiangsu section of the Yangtze River, China - Huan He; Guan-jiu Hu; Cheng Sun; Su-lan Chen; Ming-na Yang; Juan Li; Yong Zhao; Hui Wang (Environmental Science and Pollution Research, 2011)

Molecular characterization and expression analysis of elongation factors 1A and 2 from the Pacific white shrimp, Litopenaeus vannamei - Lei Wang; Yuan Liu; Wei-Na Wang; Wei-Jun Mai; Yu Xin; Jun Zhou; Wen-Yin He; An-Li Wang; Ru-Yong Sun (Molecular Biology Reports, 2011)

Molecular analysis shows differential expression of R-spondin1 in zebrafish (Danio rerio) gonads - Yanmei Zhang; Fei Li; Dongchang Sun; Jiangdong Liu; Na Liu; Qixing Yu (Molecular Biology Reports, 2011)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Species and distribution of rare earth elements in the Baotou section of the Yellow River in China - Jiang He; Chang-Wei Lü; Hong-Xi Xue; Ying Liang; Saruli Bai; Ying Sun; Li-Li Shen; Na Mi; Qing-Yun Fan (Environmental Geochemistry and Health, 2010)

Association of functional polymorphisms in MMPs genes with gastric cardia adenocarcinoma and esophageal squamous cell carcinoma in high incidence region of North China - Yan Li; Dong-lan Sun; Ya-nan Duan; Xiao-juan Zhang; Na Wang; Rong-miao Zhou; Zhi-feng Chen; Shi-jie Wang (Molecular Biology Reports, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Reciprocal regulation between M3 muscarinic acetylcholine receptor and protein kinase C-ε in ventricular myocytes during myocardial ischemia in rats - Peng-zhou Hang; Jing Zhao; Yu-ping Wang; Li-hua Sun; Yong Zhang; Li-li Yang; Na Zhao; Zhi-dan Sun; Yu-ying Mao; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Rottlerin protected dopaminergic cell line from cytotoxicity of 6-hydroxydopamine by inhibiting PKCδ phosphorylation - Ying Fan; Yan-Qiao Zhang; Dian-Jun Sun; Yi-Na Zhang; Xiao-Wei Wu; Jing Li (Neuroscience Bulletin, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

Rapid discrimination of H5 and H9 subtypes of avian influenza viruses and Newcastle disease virus by multiplex RT-PCR - Hao-tai Chen; Jie Zhang; De-hui Sun; Ji-le Zhang; Xue-peng Cai; Xiang-tao Liu; Yao-zhong Ding; Li-na Ma; Sheng-hai Yang; Lei Jin; Yongsheng Liu (Veterinary Research Communications, 2008)

Spatial distribution of Cd and Cu in soils in Shenyang Zhangshi Irrigation Area (SZIA), China - Li-na Sun; Xiao-bo Yang; Wen-qing Wang; Li Ma; Su Chen (Journal of Zhejiang University-SCIENCE B, 2008)